Preparation method and application of doped nano-barium / lithium titanate powder material

CN123022641APending Publication Date: 2026-10-30赵远云
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380062068.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-10-21
Filing Date
2023-07-24
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

The existing barium titanate/lithium titanate preparation method has problems such as uneven sintering particle size and complex equipment conditions, making it difficult to achieve large-scale, low-cost preparation. Moreover, the doping effect is uneven and cannot effectively increase the type and content of doping elements.

Method used

Using a method including initial alloy preparation, hydrogen evolution deT reaction and cation replacement, through NaOH/KOH alkaline solution treatment, in-situ endogenously doped nano-barium titanate/lithium powder was prepared, utilizing the solid state of E-type elements. Doping is achieved by dissolution and mosaic methods, and reaction conditions are controlled to obtain uniform nanoparticles.

Benefits of technology

Achieved large-scale and low-cost preparation of nano-barium titanate/lithium titanate, improved the uniformity and content of doping elements, and obtained nano-barium titanate/lithium particle powder with fine particle size and excellent morphology, which is suitable for multi-layer ceramics Capacitors and lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123022641A_ABST
    Figure CN123022641A_ABST
Patent Text Reader

Abstract

The application relates to a preparation method and application of a doped nano-barium / lithium titanate powder material. An intermetallic compound containing a doped element is used as a precursor, a non-spherical nano-titanate intermediate product is obtained through reaction of the intermetallic compound with an alkali solution, then the intermediate powder product is reacted with a barium / lithium source substance containing Ba 2+ / Li + under specific temperature, pressure and medium atmosphere for a period of time, so that the non-spherical nano-titanate intermediate product is subjected to a cation replacement reaction and a morphology change of "spheroidization", and a spherical or near-spherical in-situ endogenous doped nano-barium / lithium titanate particle powder product is obtained. The preparation method has the characteristics of simple process, easy operation and low cost, and the prepared in-situ endogenous doped nano-barium / lithium titanate powder material has a good application prospect in the fields of electronic ceramics, composite materials, coatings, powder metallurgy, multilayer ceramic capacitors, thermistors, piezoelectric ceramics, battery materials and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Preparation method and application of doped nano-barium titanate / lithium powder material Technical Field

[0001] The present invention relates to the technical field of nanomaterials, and in particular to a preparation method and application of a doped nano-barium titanate / lithium powder material. Background Art

[0002] Barium titanate (BaTiO3) is a typical perovskite crystal with high dielectric constant, low dielectric loss, high resistivity, high voltage strength and excellent insulation performance. It is an important basic raw material for multilayer ceramic capacitors (MLCC). On the basis of barium titanate, the performance of MLCC can be further improved by doping various elements such as rare earth elements. Lithium titanate (Li4Ti5O 12 ) is a type of lithium-titanium composite oxide with a spinel structure. In the field of battery materials, it has the advantages of good cycle performance, high chemical stability, low hygroscopicity in the fully charged state, and strong thermal stability. It can be used in the stable voltage range of most liquid electrolytes and is widely used in lithium-ion batteries, asymmetric supercapacitors and other fields. At present, the main methods for preparing barium / lithium titanate are: solid-phase synthesis, chemical precipitation, hydrothermal method, sol-gel method, and alcohol salt hydrolysis method. These methods either have uneven sintering particle size or require complex equipment conditions, which are not conducive to the large-scale and low-cost preparation of barium / lithium titanate.

[0003] Currently, the main effective methods for preparing doped barium titanate particles are hydrothermal and sol-gel methods. Since both methods first create a gel or suspension containing a barium titanate precursor, the desired doping substance can be added during this process, followed by hydrothermal treatment or sintering to obtain the doped barium titanate powder. However, these doping methods only achieve uniform doping of a portion of the doped substance. Developing new doping pathways and methods to significantly and cost-effectively increase the variety of dopants and doping content is of great significance for the application of doped barium titanate.

[0004] Summary of the Invention

[0005] Based on this, it is necessary to provide a large-scale and low-cost preparation method of doped nano-barium / lithium titanate to address the above problems.

[0006] A method for preparing doped nano-barium titanate / lithium powder, characterized by comprising the following steps:

[0007] Step 1: preparing an initial alloy, wherein the initial alloy comprises a T element, a Ti element, and an E element, and the phase composition of the initial alloy comprises a T-Ti(E) intermetallic compound in which the E element is solid-dissolved or a T-Ti-E intermetallic compound containing the E element; wherein, in the T-Ti(E) intermetallic compound or the T-Ti-E intermetallic compound, the molar ratio of the E element to the Ti element is 0≤C E / C Ti ≤0.30; T-type elements include at least one of Al and Zn; E-type elements include at least one of Zr, Hf, Cr, V, Nb, Ta, W, Mo, Mn, Fe, Ni, Co, Sn, Pb, Bi, B, Be, Au, Pt, Pd, Ru, Rh, Re, Os, Ir, Ag, Cu, and RE; wherein RE includes at least one rare earth element;

[0008] Step 2: The initial alloy undergoes a hydrogen evolution and de-tantalum reaction with an alkaline solution mainly composed of NaOH / KOH to obtain an intermediate powder product, which mainly comprises at least one of a nano sodium / potassium titanate thin film powder in situ endogenously doped with an E-type element, a nano porous sodium / potassium titanate irregular powder in situ endogenously doped with an E-type element, and a nano sodium / potassium titanate tube (rod) in situ endogenously doped with an E-type element;

[0009] Alternatively, the intermediate powder product composed of the nano-sodium / potassium titanate in situ endogenously doped with E-type elements is reacted with a dilute acid to obtain a hydrogen ion-substituted nano-titanate intermediate powder product in situ endogenously doped with E-type elements, the intermediate powder product mainly comprising at least one of a nano-titanate thin film powder in situ endogenously doped with E-type elements, a nano-porous titanate irregular powder in situ endogenously doped with E-type elements, and a nano-titanate tube (rod) in situ endogenously doped with E-type elements;

[0010] Step 3: Mix the intermediate powder product with Ba 2+ / Li + The barium / lithium source material is reacted for a period of time under a specific temperature, pressure and medium atmosphere, so that the above-mentioned non-spherical intermediate powder product undergoes a cation replacement reaction and a "spheroidization" morphology change, thereby obtaining a spherical or nearly spherical nano-barium titanate / lithium particle powder product that is in situ endogenously doped with E-type elements;

[0011] In the step 1,

[0012] Further, the T-type element includes Al; further, the T-type element is Al;

[0013] Further, the T-type element includes Zn; further, the T-type element is Zn;

[0014] Furthermore, the T-type elements include Al and Zn;

[0015] Further, the RE comprises at least one of the rare earth elements Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu;

[0016] Furthermore, the E-type elements include at least one of Zr, Hf, Cr, V, Nb, Ta, W, Mo, Mn, Sn, Pb, Bi, B, Be, and RE;

[0017] Furthermore, the E-type element includes at least one of Zr, Hf, Cr, V, Nb, Ta, W, and Mo;

[0018] Furthermore, the E-type element includes at least one of Mn, Sn, Pb, Bi, B, and Be;

[0019] Furthermore, the E-type elements mainly include Ag, and the atomic percentage content of Ag in the E-type elements is higher than 50%;

[0020] Furthermore, the E-type elements mainly include RE;

[0021] Furthermore, when C E / C Ti = 0, that is, the initial alloy does not contain E-type elements; in this case, the subsequent product does not contain doped E-type elements;

[0022] Furthermore, 0≤C E / C Ti ≤0.25; further, 0≤C E / C Ti ≤0.20; further, 0≤C E / C Ti ≤0.10;

[0023] Furthermore, 0 <C E / C Ti ≤0.30; further, 0 <C E / C Ti ≤0.25; further, 0 <C E / C Ti ≤0.20; further, 0 <C E / C Ti ≤0.10;

[0024] Furthermore, the phase composition of the initial alloy mainly consists of a T-Ti(E) intermetallic compound in which an E-type element is solid-dissolved or a T-Ti-E intermetallic compound containing an E-type element;

[0025] Furthermore, the T-Ti(E) intermetallic compound having a solid solution of an E-type element means that atoms of the E-type element exist in the lattice gap of the T-Ti(E) intermetallic compound in the form of interstitial atoms, or that atoms of the E-type element replace T atom positions or Ti atom positions in the lattice of the T-Ti(E) intermetallic compound in the form of substitution atoms;

[0026] Furthermore, the solid solution includes interstitial solid solution and substitutional solid solution;

[0027] Furthermore, the T-Ti-E intermetallic compound containing E-type elements refers to an intermetallic compound composed of T-type elements, Ti elements, and E-type elements, which is different from the T-Ti(E) intermetallic compound. In the T-Ti(E) intermetallic compound, the E-type elements are solid-dissolved in the T-Ti intermetallic compound; while in the T-Ti-E intermetallic compound, the E-type elements are the key components of the T-Ti-E intermetallic compound phase;

[0028] Furthermore, when C E / C Ti = 0, the T-Ti(E) intermetallic compound does not contain E-type elements and is a T-Ti intermetallic compound;

[0029] Furthermore, the initial alloy is prepared by solidifying a melt containing T elements, Ti elements, and E elements, and a solidified structure containing a T-Ti(E) intermetallic compound or a T-Ti-E intermetallic compound is formed during the solidification process of the alloy; wherein the E elements are mainly dissolved in the T-Ti(E) intermetallic compound;

[0030] Furthermore, the solidification rate of the initial alloy melt is 0.01K / s to 10 8 K / s;

[0031] Furthermore, generally speaking, the higher the cooling rate, the higher the solid solubility of the E-type elements in the T-Ti(E) intermetallic compound. At this time, the solid solubility of non-equilibrium solidification can be much higher than the solid solubility corresponding to equilibrium solidification.

[0032] Further, the T-Ti(E) intermetallic compound includes at least one of T3Ti(E), T2Ti(E), and TTi(E) intermetallic compounds;

[0033] Further, in the initial alloy, the T-Ti(E) intermetallic compound is composed of one or more daughter T-Ti(E) intermetallic compounds;

[0034] Furthermore, the shape of the initial alloy has an average size in any three-dimensional direction greater than 2 μm;

[0035] Furthermore, the shape of the initial alloy has an average size in any three-dimensional direction greater than 5 μm;

[0036] Furthermore, the shape of the initial alloy has an average size in any three-dimensional direction greater than 10 μm;

[0037] Furthermore, the shape of the initial alloy includes at least one of block, granular, filament, strip, ribbon, and sheet;

[0038] Furthermore, the initial alloy is in powder or strip form, and the powder particles or strips have at least one dimension smaller than 5 mm in three dimensions;

[0039] Furthermore, the initial alloy powder particles or strips have at least one dimension smaller than 500 μm in the three-dimensional direction;

[0040] Preferably, the initial alloy powder particles or strips have at least one dimension smaller than 200 μm in the three-dimensional direction;

[0041] Preferably, the initial alloy powder particles or strips have at least one dimension smaller than 50 μm in three dimensions;

[0042] Further, when the initial alloy is in the form of a strip, it can be prepared by a method including a melt spinning strip method;

[0043] Furthermore, when the initial alloy is in powder form, a larger initial alloy ingot can be prepared by a casting method and then crushed into initial alloy powder.

[0044] In the step 2,

[0045] Furthermore, the alkaline solution comprises at least one of NaOH and KOH solutions;

[0046] Preferably, the solvent in the alkaline solution is mainly water;

[0047] Furthermore, the concentration of the alkali in the alkaline solution is 2.1 to 30 mol / L; preferably, the concentration of the alkali in the alkaline solution is 2.1 to 15 mol / L;

[0048] Furthermore, the concentration of the alkali solution refers to the effective concentration of NaOH / KOH in the alkali; the present application found that only the effective concentration of NaOH / KOH is meaningful. Specifically, when there is OH in the alkali solution - When it comes from relatively weak bases such as LiOH, RbOH, Ba(OH)2, Ca(OH)2, and Sr(OH)2, although the total OH - The content is higher than the OH contributed by NaOH and KOH -Content, but this part of the OH contributed by the weak base - The content has no obvious effect when the initial alloy forms the specific intermediate powder product described in step 2 through hydrogen evolution and de-T reaction.

[0049] Furthermore, the NaOH / KOH in the alkaline solution reacting with the initial alloy is in excess dosage, so that the reaction can be carried out at a higher alkali concentration.

[0050] Furthermore, the NaOH / KOH content in the alkaline solution reacting with the initial alloy exceeds 5 times the required reaction dosage;

[0051] Furthermore, the content of NaOH / KOH in the alkaline solution reacting with the initial alloy exceeds 10 times the required reaction amount;

[0052] The higher the concentration of NaOH / KOH and the higher the temperature, the more intense the reaction with the initial alloy;

[0053] The hydrogen evolution and de-T reaction refers to the reaction in which the initial alloy reacts with the NaOH / KOH solution, and the T is dissolved by the alkali and converted into salt and enters the solution, while releasing hydrogen.

[0054] Furthermore, the initial alloy reacts with an alkaline solution mainly composed of NaOH / KOH, and different intermediate powder products are obtained under different reaction conditions:

[0055] 1) Under normal pressure, when the concentration of NaOH / KOH is high and the temperature of the alkaline solution is high, the intermediate powder product mainly includes nano-sodium / potassium titanate thin film powder in situ endogenously doped with E-type elements;

[0056] Preferably, by controlling the concentration and temperature of NaOH / KOH, during the reaction between the initial alloy and the alkaline solution mainly composed of NaOH / KOH, when the reaction interface advances inward from the surface of the initial alloy at an average rate greater than 10 μm / min, the intermediate powder product mainly includes nano-sodium / potassium titanate thin film powder in situ endogenously doped with E-type elements;

[0057] Preferably, when the concentration of NaOH / KOH is in the range of 5.1 to 30 mol / L, the temperature of the alkaline solution is greater than 100°C, but not higher than the boiling point T of the alkaline solution at this concentration. f溶液 When the intermediate powder products mainly include nano-sodium / potassium titanate thin film powders in situ endogenously doped with E-type elements;

[0058] As a preference, when the concentration of NaOH / KOH is in the range of 7.5 to 30 mol / L and the temperature is the boiling point T of the alkaline solution at this concentration, f溶液 When the intermediate powder products mainly include nano-sodium / potassium titanate thin film powders in situ endogenously doped with E-type elements;

[0059] Under normal pressure, the boiling point of water is 100℃; when alkali is dissolved in water, the boiling point of the alkali solution under 1 standard atmospheric pressure is higher than 100℃, and the higher the concentration of the alkali, the higher the boiling point. For example, the molar concentration of 5.1mol / L sodium hydroxide aqueous solution has a boiling point T f溶液 About 108℃; molar concentration 7mol / L sodium hydroxide aqueous solution, boiling point T f溶液 About 112℃; molar concentration of 10mol / L sodium hydroxide aqueous solution, boiling point T f溶液 About 119℃; molar concentration of 12mol / L sodium hydroxide aqueous solution, boiling point T f溶液 About 128℃; molar concentration of 15mol / L sodium hydroxide aqueous solution, boiling point T f溶液 About 140℃; molar concentration of 17mol / L sodium hydroxide aqueous solution, boiling point T f溶液 About 148℃; molar concentration of 20mol / L sodium hydroxide aqueous solution, boiling point T f溶液 About 160℃; molar concentration 25mol / L sodium hydroxide aqueous solution, boiling point T f溶液 About 180℃; molar concentration of 10mol / L potassium hydroxide aqueous solution, boiling point T f溶液 About 125℃; molar concentration of 12mol / L potassium hydroxide aqueous solution, boiling point T f溶液 About 136℃; molar concentration of 15mol / L potassium hydroxide aqueous solution, boiling point T f溶液 About 150℃;

[0060] During the reaction, the initial alloy undergoes nano-fragmentation through a violent hydrogen evolution and de-tantalum reaction, and then undergoes shape and composition reconstruction to generate nano-sodium / potassium titanate thin film powders in situ endogenously doped with E-type elements.

[0061] The nano-fragmentation and shape and composition reconstruction refers to the fragmentation of the T-Ti(E) intermetallic compound phase or the T-Ti-E intermetallic compound phase in the initial alloy into a nano-sodium / potassium titanate film with at least one dimension (i.e., thickness) less than 5 nm in the three-dimensional direction through hydrogen evolution and T removal reaction;

[0062] Furthermore, the thickness of the nano-sodium / potassium titanate film in-situ doped with E-type elements is less than 5 nm;

[0063] Furthermore, the thickness of the nano-sodium / potassium titanate film in situ endogenously doped with E-type elements ranges from 0.25 nm to 4 nm;

[0064] Furthermore, the thickness of the nano-sodium / potassium titanate film in situ endogenously doped with E-type elements ranges from 0.25 nm to 3 nm;

[0065] Furthermore, the average area of ​​the nano-sodium / potassium titanate film in situ endogenously doped with E-type elements is greater than 500nm 2 ;

[0066] Furthermore, the average area of ​​the nano-sodium / potassium titanate film in situ doped with E-type elements is greater than 1000nm 2 ;

[0067] Furthermore, the average area of ​​the nano-sodium / potassium titanate film in situ endogenously doped with E-type elements is greater than 10000nm 2 ;

[0068] Furthermore, the nano-sodium / potassium titanate film in-situ endogenously doped with E-type elements is in a low crystalline state;

[0069] Furthermore, the initial alloy undergoes a hydrogen evolution and titanate removal reaction with an alkaline solution mainly composed of NaOH / KOH to obtain an intermediate powder product, the composition of which mainly includes nano-sodium / potassium titanate thin film powder in situ endogenously doped with E-type elements;

[0070] The nano-sodium / potassium titanate thin film powder refers to a powder morphology from a macroscopic point of view; but from a microscopic point of view, the powder is composed of a large number of thin films;

[0071] 2) Under normal pressure, when the concentration of NaOH / KOH is low and the temperature of the alkaline solution is low, the intermediate powder product mainly includes irregular nanoporous sodium / potassium titanate powders in situ endogenously doped with E-type elements;

[0072] Preferably, by controlling the concentration and temperature of NaOH / KOH, during the reaction of the initial alloy with the alkaline solution mainly composed of NaOH / KOH, when the reaction interface advances inward from the surface of the initial alloy at an average rate of less than 2 μm / min, the intermediate powder product mainly includes irregular nanoporous sodium / potassium titanate powders in situ endogenously doped with E-type elements;

[0073] Preferably, when the concentration of NaOH / KOH is in the range of 2.1 to 15 mol / L and the temperature is less than 60°C, the intermediate powder product mainly comprises irregular nanoporous sodium / potassium titanate powder in situ endogenously doped with E-type elements;

[0074] The irregular powder refers to the powder particles that have undergone a certain degree of initial fragmentation due to the generation of hydrogen during the reaction of the initial alloy. Since the fragmentation is random and irregular, the powder particles after fragmentation are of different sizes and shapes, and are irregular powders.

[0075] If the volume of irregular powder particles is equivalent to that of nearly spherical particles, then:

[0076] Furthermore, the D90 particle size of the nanoporous sodium / potassium titanate irregular powder in situ endogenously doped with E-type elements is greater than 500 nm;

[0077] Furthermore, the D90 particle size of the nanoporous sodium / potassium titanate irregular powder in situ endogenously doped with E-type elements is greater than 1 μm;

[0078] Furthermore, the D90 particle size of the nanoporous sodium / potassium titanate irregular powder in situ endogenously doped with E-type elements is greater than 3 μm;

[0079] Furthermore, the average diameter of the ligaments in the nanoporous sodium / potassium titanate microstructure in the nanoporous sodium / potassium titanate irregular powder in situ endogenously doped with E-type elements is less than 10 nm;

[0080] Furthermore, the average diameter of the ligaments in the nanoporous sodium / potassium titanate microstructure in the nanoporous sodium / potassium titanate irregular powder in situ endogenously doped with E-type elements is less than 5 nm;

[0081] Furthermore, the average diameter of the ligaments in the nanoporous sodium / potassium titanate microstructure in the nanoporous sodium / potassium titanate irregular powder in situ endogenously doped with E-type elements is less than 3 nm;

[0082] Furthermore, the nanoporous sodium / potassium titanate irregular powder in situ endogenously doped with E-type elements is mainly in a low crystalline state;

[0083] 3) Under normal pressure, at a medium concentration of NaOH / KOH and a medium temperature of the alkaline solution, the intermediate powder products mainly include irregular nanoporous sodium / potassium titanate powders in situ endogenously doped with E-type elements and nano sodium / potassium titanate thin film powders in situ endogenously doped with E-type elements;

[0084] Preferably, by controlling the concentration and temperature of NaOH / KOH, during the reaction of the initial alloy with the alkaline solution mainly composed of NaOH / KOH, when the reaction interface advances inward from the surface of the initial alloy at an average rate of 2 μm / min-10 μm / min, the intermediate powder product mainly includes nanoporous sodium / potassium titanate irregular powder in situ endogenously doped with E-type elements and nano sodium / potassium titanate thin film powder in situ endogenously doped with E-type elements;

[0085] Preferably, when the concentration of NaOH / KOH is in the range of 2.1 to 15 mol / L and the temperature of the alkaline solution is 60°C to 100°C, the intermediate powder product mainly includes irregular nanoporous sodium / potassium titanate powder in situ endogenously doped with E-type elements and nano sodium / potassium titanate thin film powder in situ endogenously doped with E-type elements;

[0086] Furthermore, the irregular powder of nano-porous sodium / potassium titanate doped with E elements in-situ and the powder of nano-sodium / potassium titanate film doped with E elements in-situ are mainly in a low-crystalline state;

[0087] In the above 1)-3), the reaction time for the complete removal of element T from the initial alloy is related to the shape of the initial alloy: when the initial alloy powder particles are smaller, or the initial alloy strip is thinner, the time required for the hydrogen evolution and T removal reaction to complete is shorter; conversely, the time required for the hydrogen evolution and T removal reaction to complete is longer. According to the average advancing rate of the reaction interface and the size of the initial alloy, the minimum reaction time t required for the hydrogen evolution and T removal reaction to complete can be calculated. For example, when the initial alloy is in the form of a strip with a thickness of d and the average advancing rate of the reaction interface is v, considering that the reaction interface advances from both the upper and lower surfaces of the strip, t = 0.5d / v; similarly, when the initial alloy is in the form of particles with a diameter of d and the average advancing rate of the reaction interface is v, t = 0.5d / v.

[0088] When the NaOH concentration is 10 mol / L, generally, during the reaction of the initial alloy with the alkali solution, the advancing rate of the hydrogen evolution and T removal reaction interface from the surface of the initial alloy inward is as follows:

[0089] When 60°C ≤ T1 ≤ 80°C, the average advancing rate of the reaction interface is about 2 μm / min - 7 μm / min;

[0090] When 80°C ≤ T1 ≤ 90°C, the average advancing rate of the reaction interface is about 7 μm / min - 15 μm / min;

[0091] When 90°C < T1 ≤ 100°C, the average advancing rate of the reaction interface is about 15 μm / min - 30 μm / min;

[0092] When 100°C < T1 ≤ 110°C, the average advancing rate of the reaction interface is about 30 μm / min - 50 μm / min;

[0093] When 110°C < T1 < 119°C, the average advancing rate of the reaction interface is about 50 μm / min - 120 μm / min;

[0094] If the average rate of the reaction interface advancement of the initial alloy strip is about ~120 μm / min (reacting at the boiling point T of NaOH concentration of 10 mol / L), that is, for a 40-μm-thick initial alloy strip, the hydrogen evolution and Al removal reaction can be completed in 10 s; for a 20-μm-thick initial alloy strip, the hydrogen evolution and Al removal reaction can be completed in 5 s; even for an initial alloy ball with a diameter of 5 mm, the hydrogen evolution and Al removal reaction can be completed in 21 min; f溶液 temperature reaction),

[0095] Furthermore, the reaction time of the initial alloy and the alkaline solution is 10s to 59min;

[0096] Furthermore, the reaction time of the initial alloy and the alkaline solution is 10s to 9.9min;

[0097] Furthermore, the reaction time of the initial alloy and the alkaline solution is 10s to 2min;

[0098] Furthermore, the reaction time of the initial alloy and the alkaline solution is 10s to 1min;

[0099] Furthermore, the reaction time of the initial alloy and the alkaline solution is 10s to 30s;

[0100] Obviously, when T1 is higher, the thickness of the initial alloy is thinner or the particle size is smaller, the required reaction time is shorter; conversely, the reaction time is longer;

[0101] After the hydrogen evolution and de-TiO reaction is complete, the reaction system reaches equilibrium. At this point, further extending the holding time of the reaction system at the original reaction temperature can still ensure the stability of the intermediate product. Therefore, when the reaction time of the initial alloy and the alkaline solution exceeds the minimum required hydrogen evolution and de-TiO reaction time t, such as several hours, the corresponding intermediate product can still be obtained.

[0102] 5) The reaction is carried out in a closed container at a pressure higher than normal, with a high concentration of NaOH / KOH and a temperature higher than the boiling point T at one atmosphere. f溶液 At temperature, the intermediate powder products mainly include nano-sodium / potassium titanate tubes (rods) in situ endogenously doped with E-type elements;

[0103] Furthermore, the reaction temperature is higher than T f溶液 Temperature, lower than 300 ° C; further, the reaction temperature is higher than T f 溶液 Temperature, lower than 250 ° C; further, the reaction temperature is higher than T f溶液 Temperature, below 200°C;

[0104] Further, the reaction time is 1 min-5 h; further, the reaction time is 1 min-2 h; further, the reaction time is 1 min-30 min;

[0105] As a preference, when the NaOH / KOH concentration range is 7.5 to 30 mol / L and the reaction temperature is higher than T f溶液 , when the gas pressure is the pressure corresponding to the closed container at the corresponding temperature, the intermediate powder product mainly includes nano sodium / potassium titanate tubes (rods) in situ endogenously doped with E-type elements;

[0106] Furthermore, the outer diameter of the nano sodium / potassium titanate tube (rod) in situ endogenously doped with E-type elements does not exceed 10 nm;

[0107] Furthermore, the outer diameter of the nano sodium / potassium titanate tube (rod) in situ endogenously doped with E-type elements does not exceed 7.5 nm;

[0108] Furthermore, the nano-sodium / potassium titanate tubes (rods) in-situ endogenously doped with E-type elements are mainly in a crystalline state;

[0109] 6) reacting the intermediate powder products composed of the nano-sodium / potassium titanates of different shapes in situ endogenously doped with E-type elements described in 1) to 4) above with dilute acid to obtain hydrogen ion-substituted nano-titanate intermediate powder products in situ endogenously doped with E-type elements, the intermediate powder products mainly comprising at least one of nano-titanate thin film powders in situ endogenously doped with E-type elements, nano-porous titanate irregular powders in situ endogenously doped with E-type elements, and nano-titanate tubes (rods) in situ endogenously doped with E-type elements;

[0110] Furthermore, the hydrogen ion concentration in the acid solution is 0.001 mol / L to 0.2 mol / L;

[0111] Preferably, the hydrogen ion concentration in the acid solution is 0.001 mol / L to 0.1 mol / L;

[0112] Preferably, the hydrogen ion concentration in the acid solution is 0.001 mol / L to 0.05 mol / L;

[0113] Furthermore, except that the cations are changed from sodium / potassium ions to hydrogen ions, the various morphological features of the nano titanate film powder in situ endogenously doped with E-type elements are basically the same as those of the nano sodium / potassium titanate film powder in situ endogenously doped with E-type elements; the various morphological features of the nano porous titanate irregular powder in situ endogenously doped with E-type elements are basically the same as those of the nano porous sodium / potassium titanate irregular powder in situ endogenously doped with E-type elements; the various morphological features of the nano titanate tubes (rods) in situ endogenously doped with E-type elements are basically the same as those of the nano sodium / potassium titanate tubes (rods) in situ endogenously doped with E-type elements; the specific features are described above;

[0114] In particular, during the reaction of the initial alloy with the alkaline solution mainly composed of NaOH / KOH, or during the reaction of 1) to 5) above, since the E-type elements are initially dissolved in the T-Ti(E) intermetallic compound in the form of E atoms, or the E-type atoms are dispersed in the T-Ti-E intermetallic compound, the T-Ti(E) intermetallic compound or the T-Ti-E intermetallic compound remains in a solid state before and after the reaction with the NaOH / KOH solution; therefore, the E-type element atoms cannot be easily expelled therefrom during the reaction, resulting in the in-situ endogenous doping of the E-type elements in the intermediate powder product; depending on the reaction conditions, sodium / potassium titanate or titanate intermediate powder products with different morphologies that are in-situ endogenously doped with the E-type elements are ultimately obtained;

[0115] Furthermore, the basic methods of in-situ endogenous doping of the E-type elements mainly include at least one of the following two methods a) and b):

[0116] c) The E-type elements are in situ endogenously embedded in the sodium / potassium titanate or titanate intermediate powder product in the form of E nanoparticles or oxidized E nanoparticles; at this time, the E nanoparticles or oxidized E nanoparticles are in a different phase relative to the sodium / potassium titanate or titanate matrix;

[0117] d) E-type elements are in situ endogenized in the form of E atoms or atomic clusters in the sodium / potassium titanate or titanate intermediate powder product; at this time, the E atoms or atomic clusters fail to form a different phase or fail to form a clear different phase relative to the sodium / potassium titanate or titanate matrix; wherein the size of the E atomic cluster does not exceed 2nm, and its contrast is difficult to distinguish under TEM electron microscope observation. In this case, the E-type elements exist in the form of E atoms or atomic clusters in the sodium / potassium titanate or titanate intermediate powder product in the form of solid solution; this method of in situ endogenous doping through solid solution includes at least one of intermittent solid solution and substitutional solid solution; further, this method of in situ endogenous doping through solid solution is mainly substitutional solid solution, that is, doping E-type atoms to replace certain atoms in the lattice of sodium / potassium titanate or titanate;

[0118] The in-situ endogenous embedding or in-situ endogenization refers to the E nanoparticles or oxidized E nanoparticles being embedded and distributed in the sodium / potassium titanate or titanate matrix by in-situ embedding, that is, the E nanoparticles or oxidized E nanoparticles are embedded in situ by being partially or completely wrapped by the sodium / potassium titanate or titanate matrix, without relying on external addition or external mixing to embed them therein; the in-situ embedded E nanoparticles or oxidized E nanoparticles cannot move freely in the sodium / potassium titanate or titanate matrix, nor will they be easily peeled off. This in-situ endogenous embedding is completed by the simultaneous embedding of the E nanoparticles or oxidized E nanoparticles and the sodium / potassium titanate or titanate matrix during the hydrogen evolution and de-T reaction;

[0119] The same is true when the E-type elements are in situ embedded in the sodium / potassium titanate or titanate intermediate powder product in the form of E atoms or atomic clusters.

[0120] Generally speaking, the basic mode of in-situ endogenous doping of E-type elements is related to the solid solubility of E-type elements in sodium / potassium titanate or titanate matrix. When the solid solubility of E-type elements in sodium / potassium titanate or titanate matrix is ​​high, they are mainly in-situ endogenous doped in the form of E atoms or atomic clusters. When the solid solubility of E-type elements in sodium / potassium titanate or titanate matrix is ​​low, they are mainly in-situ endogenous doped in the form of E nanoparticles or oxidized E nanoparticles.

[0121] In addition, the basic method of in-situ endogenous doping of E-type elements is also similar to that of C E / C Ti Related, the same type of E elements, when C E / C Ti When the value is low, it is mainly in situ embedded doping in the form of E atoms or atomic clusters; when C E / C Ti When the low and high values ​​are taken, it is mainly in situ endogenous mosaic doping in the form of E nanoparticles or oxidized E nanoparticles;

[0122] Furthermore, when the E-type elements mainly include at least one of Au, Pt, Pd, Ru, Rh, Re, Os, and Ir, and:

[0123] 0.03 <C E / C Ti When ≤0.30, the E-type elements are mainly embedded in the sodium / potassium titanate or titanate intermediate powder product in the form of E nanoparticles; and the particle size of the E nanoparticles is 2nm-20nm;

[0124] 0.01 <C E / C Ti When the concentration is ≤0.03, the E-type elements are embedded in the sodium titanate / potassium titanate intermediate powder product in the form of E nanoparticles and E atoms or atomic clusters;

[0125] 0 <C E / C Ti When ≤0.01, the E-type elements are mainly in situ endogenously doped into the sodium / potassium titanate or titanate intermediate powder products in the form of E atoms or atomic clusters;

[0126] Furthermore, when the E-type elements mainly include at least one of Cu, Fe, Ni, and Co, and:

[0127] 0.05 <C E / C TiWhen ≤0.30, the E-type elements are mainly in situ embedded in the sodium / potassium titanate or titanate intermediate powder product in the form of E nanoparticles or oxidized E nanoparticles; and the particle size of the E nanoparticles is 2nm-20nm;

[0128] 0.02 <C E / C Ti When the concentration is ≤0.05, the E-type elements are in situ embedded in the sodium / potassium titanate or titanate intermediate powder product in the form of E nanoparticles or oxidized E nanoparticles, as well as in the form of E atoms or atomic clusters;

[0129] 0 <C E / C Ti When ≤0.02, the E-type elements are mainly in situ endogenously doped into the sodium / potassium titanate or titanate intermediate powder products in the form of E atoms or atomic clusters;

[0130] Furthermore, when the E-type elements mainly include Ag, and:

[0131] 0.20 <C E / C Ti When ≤0.30, the E-type elements are mainly embedded in the sodium / potassium titanate or titanate intermediate powder product in the form of E nanoparticles; and the particle size of the E nanoparticles is 2nm-20nm;

[0132] 0.10 <C E / C Ti When ≤0.20, the E-type elements are in situ embedded in the sodium / potassium titanate or titanate intermediate powder products in the form of E nanoparticles, E atoms or atomic clusters;

[0133] 0 <C E / C Ti When ≤0.10, the E-type elements are mainly in situ endogenously doped into the sodium / potassium titanate or titanate intermediate powder products in the form of E atoms or atomic clusters;

[0134] Furthermore, when the E-type elements mainly include at least one of Zr and Hf, and:

[0135] 0 <C E / C Ti When ≤0.30, the E-type elements are mainly in situ endogenously doped into the sodium / potassium titanate or titanate intermediate powder products in the form of E atoms or atomic clusters;

[0136] As a preference, 0 <C E / C Ti When ≤0.10, the E-type elements are mainly in situ endogenously doped into the sodium / potassium titanate or titanate intermediate powder products in the form of E atoms or atomic clusters;

[0137] Because Ti, Zr and Hf are in the same group on the periodic table and have similar properties, Zr and Hf can be doped into sodium / potassium titanate or titanic acid at a higher content;

[0138] Furthermore, when the E-type elements mainly include at least one of Cr, V, Nb, Ta, W, and Mo, and:

[0139] 0.20 <C E / C Ti When ≤0.30, the E-type elements are in situ embedded in the sodium / potassium titanate or titanate intermediate powder product in the form of E nanoparticles or oxidized E nanoparticles, as well as in the form of E atoms or atomic clusters;

[0140] 0 <C E / C Ti When ≤0.20, the E-type elements are mainly in situ endogenously doped into the sodium / potassium titanate or titanate intermediate powder products in the form of E atoms or atomic clusters;

[0141] As a preference, 0 <C E / C Ti When ≤0.10, the E-type elements are mainly in situ endogenously doped into the sodium / potassium titanate or titanate intermediate powder products in the form of E atoms or atomic clusters;

[0142] Because Ti has similar properties to Cr, V, Nb, Ta, W, and Mo, Cr, V, Nb, Ta, W, and Mo can be doped in sodium / potassium titanate or titanic acid at a relatively high content;

[0143] Furthermore, when the E-type elements mainly include at least one of Mn, Sn, Pb, Bi, B, Be, and RE, and:

[0144] 0.10 <C E / C Ti When ≤0.30, the E-type elements are mainly in situ embedded in the sodium / potassium titanate or titanate intermediate powder product in the form of E nanoparticles or oxidized E nanoparticles; and the particle size of the E nanoparticles is 2nm-20nm;

[0145] 0.06 <C E / C Ti When ≤0.10, the E-type elements are in situ embedded in the sodium / potassium titanate or titanate intermediate powder product in the form of E nanoparticles or oxidized E nanoparticles, as well as in the form of E atoms or atomic clusters;

[0146] 0 <C E / C Ti When ≤0.06, the E-type elements are mainly in situ endogenously doped into the sodium / potassium titanate or titanate intermediate powder products in the form of E atoms or atomic clusters;

[0147] As a preference, 0 <C E / C Ti When ≤0.03, the E-type elements are mainly in situ endogenously doped into the sodium / potassium titanate or titanate intermediate powder products in the form of E atoms or atomic clusters.

[0148] illustrate:

[0149] The sodium / potassium titanate refers to "sodium titanate or (and) potassium titanate", and can also be expressed as "at least one of sodium titanate and potassium titanate"; it can also be expressed as sodium titanate (potassium) in which potassium is solid-dissolved in sodium titanate or potassium titanate (sodium) in which sodium is solid-dissolved in potassium titanate.

[0150] The NaOH / KOH represents NaOH or (and) KOH, and can also be represented by at least one of NaOH and KOH;

[0151] In the step three,

[0152] Ba 2+ / Li + Means "Ba 2+ or (and) Li + ", which can also be expressed as "Ba 2+ 、Li + at least one of";

[0153] The Ba 2+ / Li + The barium / lithium source materials include Ba 2+ / Li + Alkali, containing Ba 2+ / Li + at least one of the salts of

[0154] Furthermore, the Ba-containing 2+ / Li + The base comprises at least one of Ba(OH)2 and LiOH;

[0155] Furthermore, the Ba-containing 2+ / Li + The alkali mainly contains Ba 2+ , and it is mainly composed of Ba(OH)2;

[0156] Furthermore, the Ba-containing 2+ / Li + The base mainly contains Li + , and it is mainly composed of LiOH;

[0157] Furthermore, the Ba-containing 2+ / Li +The salt includes at least one of water-soluble BaCl2, LiCl, Ba(NO3)2, LiNO3, and Li2SO4;

[0158] Furthermore, the Ba-containing 2+ / Li + The salt includes at least one of Li3PO4, Ba3(PO4)2, Li2CO3, BaCO3, BaSO4, and BaS that are poorly water-soluble;

[0159] Furthermore, when the medium atmosphere is a solution, the Ba 2+ / Li + The barium / lithium source material is mainly a water-soluble salt or base, which includes at least one of Ba(OH)2, LiOH, BaCl2, LiCl, Ba(NO3)2, LiNO3, and Li2SO4;

[0160] Furthermore, when the medium atmosphere is a solution, the Ba 2+ / Li + The barium / lithium source material is mainly at least one of water-soluble Ba(OH)2 and LiOH;

[0161] Furthermore, when the medium atmosphere is non-solution, step three is specifically: mixing the intermediate powder product of step two with a Ba-containing 2+ / Li + The barium / lithium source material is ball-milled and sand-milled to mix, and then solid-phase reaction is carried out; wherein, Ba in the reaction system 2+ / Li + The ratio of the molar content of the intermediate powder product to the molar content of Ti is in the range of 0.75:1 to 1.25:1; after the reaction is completed, the mixture is crushed and dispersed by ball milling or sand milling to obtain a nano-barium titanate / lithium particle powder product endogenously doped with E-type elements in situ;

[0162] Furthermore, when the medium atmosphere is a non-solution, the Ba 2+ / Li + The barium / lithium source material is mainly at least one of the poorly water-soluble Li3PO4, Ba3(PO4)2, Li2CO3, BaCO3, BaSO4, and BaS;

[0163] Furthermore, when the medium atmosphere is a non-solution, the Ba 2+ / Li + The barium / lithium source material is mainly at least one of the poorly water-soluble Li3PO4, Ba3(PO4)2, Li2CO3, BaCO3, BaSO4, and BaS;

[0164] Furthermore, when the medium atmosphere is a non-solution, the Ba2+ / Li + The barium / lithium source material is mainly at least one of Li2CO3 and BaCO3 which are poorly water-soluble;

[0165] Furthermore, when the medium atmosphere is a non-solution, the temperature of the solid phase reaction is 400° C.-1500° C.;

[0166] Furthermore, when the medium atmosphere is a non-solution, the temperature of the solid phase reaction is 400° C.-1300° C.;

[0167] Furthermore, when the medium atmosphere is a non-solution, the temperature of the solid phase reaction is 600° C.-1000° C.;

[0168] Furthermore, when the medium atmosphere is a solution, the above-mentioned non-spherical intermediate powder product and the water-soluble Ba-containing 2+ / Li + The morphological changes of "spheroidization" of salts or bases and the cation replacement reaction are mainly manifested in:

[0169] During the reaction, the sodium / potassium titanate or titanic acid is replaced by barium / lithium titanate;

[0170] During the reaction, the shape of the nano-sodium / potassium titanate or titanate film powder intermediate product is "spheroidized" and transformed into spherical or nearly spherical particles with an average particle size ranging from 5nm to 300nm;

[0171] During the reaction, the shape of the nanoporous sodium / potassium titanate or irregular titanate powder intermediate product is "spheroidized" and transformed into spherical or nearly spherical particles with an average particle size ranging from 5 nm to 300 nm;

[0172] During the reaction process, the shape of the nano sodium / potassium titanate tubes (rods) or titanate tube (rod) powder intermediate product changes from a tube (rod) shape to a spherical or nearly spherical particle with an average particle size ranging from 5nm to 300nm;

[0173] During the reaction, the in-situ endogenously doped E-type elements in the intermediate powder product still remain in an in-situ endogenously doped state.

[0174] During the reaction, the process of the nano-sodium / potassium titanate or titanic acid being replaced by nano-barium / lithium titanate occurs no later than the process of the non-spherical intermediate powder product undergoing "spheroidization" morphology change; that is, the replacement reaction and "spheroidization" begin simultaneously, but the replacement reaction process can be completed first, and the morphological change process of the non-spherical intermediate powder product undergoing "spheroidization" can continue after the replacement reaction is completed;

[0175] Furthermore, the spherical or nearly spherical particles include at least one of solid spherical or nearly spherical particles and non-solid spherical or nearly spherical particles;

[0176] Furthermore, the non-solid spherical or nearly spherical particles include at least one of hollow spherical or nearly spherical particles and partially hollow spherical or nearly spherical particles;

[0177] Furthermore, the hollow spherical or nearly spherical particles include hollow spherical shell particles;

[0178] Furthermore, the partially hollow spherical or nearly spherical particles include incomplete hollow spherical shell particles;

[0179] Furthermore, the hollow or partially hollow spherical shell particles have a shell wall thickness of 3 nm to 10 nm;

[0180] Furthermore, the minimum sintering film-forming temperature of the spherical or nearly spherical nano-barium titanate / lithium particle powder product in-situ doped with E-type elements does not exceed 950°C;

[0181] Furthermore, the minimum sintering film-forming temperature of the spherical or nearly spherical nano-barium titanate / lithium particle powder product in-situ endogenously doped with E-type elements does not exceed 850° C.

[0182] In addition, when the types and contents of E-type elements in the nano sodium / potassium titanate or titanic acid in situ endogenously doped with E-type elements are different, it will also affect the "spheroidization" process of the non-spherical intermediate powder product; generally speaking, when it contains doped E-type elements, it will hinder the "spheroidization" process to a certain extent, and the higher the content of E-type elements, the more obvious the impact.

[0183] In the reaction system, the conditions for the "spheroidization" and cation replacement reaction of the non-spherical intermediate powder product are mainly:

[0184] The medium atmosphere is mainly a solution medium, the pressure is normal pressure or higher than normal pressure, and the barium / lithium source material is mainly Ba 2+ / Li + The reaction temperature is 30℃-T f溶液介质 , the reaction time is greater than 5s; among them, T f溶液介质 is the boiling point temperature of the solution medium at normal pressure, T f溶液介质 The value of Ba 2+ / Li + The type and concentration of water-soluble salts or bases are different, and the general range is 100℃-150℃;

[0185] Furthermore, the pressure is normal pressure, that is, the reaction is carried out in an open container;

[0186] Further, the barium / lithium source material comprises at least one of Ba(OH)2, LiOH, BaCl2, LiCl, Ba(NO3)2, LiNO3, and Li2SO4;

[0187] Furthermore, the barium / lithium source material comprises at least one of Ba(OH)2 and LiOH;

[0188] Furthermore, in the reaction system, Ba in the aqueous solution 2+ / Li + The total molar content C Ba / Li The molar content of Ti in nano sodium / potassium titanate or titanate powder is C Ti The ratio C Ba / Li / C Ti Satisfy 0.8≤C Ba / Li / C Ti ;

[0189] Furthermore, 1≤C Ba / Li / C Ti ; Further, 1≤C Ba / Li / C Ti ≤10;

[0190] Furthermore, the reaction temperature is 50°C-T f溶液介质 ,

[0191] Furthermore, the reaction temperature is 80°C-T f溶液介质 , further, the reaction temperature is 100℃-T f溶液介质

[0192] Further, the reaction time is 10s-10h; further, the reaction time is 10s-1h;

[0193] Furthermore, when the reaction temperature is T f溶液介质 When, the reaction time is 10s-15min;

[0194] Furthermore, when the reaction temperature is T f溶液介质 When, the reaction time is 10s-5min;

[0195] Furthermore, when the reaction temperature is T f溶液介质 When, the reaction time is 10s-2min;

[0196] Preferably, when the aqueous solution in the reaction system contains NaOH / KOH components, the reaction effect is better; in this case, NaOH / KOH acts as a catalyst;

[0197] Preferably, the total concentration of NaOH / KOH in the aqueous solution is 0.001 mol / L-25 mol / L;

[0198] Preferably, the total concentration of NaOH / KOH in the aqueous solution is 0.001 mol / L-1 mol / L;

[0199] Furthermore, when subsequent dry heat treatment is required to further promote the degree of spheroidization, the temperature of the subsequent dry heat treatment is 150°C-1300°C;

[0200] Furthermore, when subsequent dry heat treatment is required to further promote the degree of spheroidization, the temperature of the subsequent dry heat treatment is 150°C-1000°C;

[0201] During the reaction, the nano sodium / potassium titanate is replaced by nano barium / lithium titanate; or the nano titanic acid is replaced by nano barium / lithium titanate;

[0202] When the above-mentioned non-spherical intermediate powder product is mainly an intermediate product of nano-sodium / potassium titanate or titanate film powder in situ endogenously doped with E-type elements, its primary "spheroidization" process and mechanism are as follows:

[0203] In the reaction system solution, when the nano-sodium / potassium titanate or titanate film in situ endogenously doped with E-type elements is a single free film, the nano-sodium / potassium titanate or titanate is replaced by nano-barium / lithium titanate at the same time and thereafter, the film undergoes a spherical shrinkage process, becoming a single spherical or nearly spherical particle; when the primary "spheroidization" is not complete, non-solid spherical or nearly spherical shell particles are obtained by shrinking the film, and the outer diameter of the particle is in the range of 5nm-150nm; when the "spheroidization" is complete, the non-solid spherical or nearly spherical shell particles are further condensed into nearly solid spherical or nearly spherical particles, and the particle size is in the range of 2nm-30nm, depending on the size of the original film; further, the particle size is in the range of 2nm-20nm;

[0204] Therefore, for a single free nano-sodium / potassium titanate or titanate film, its spheroidization process can be roughly summarized as: film → non-solid spherical shell → solid sphere;

[0205] Furthermore, the spherical or nearly spherical particles include at least one of solid spherical or nearly spherical particles and non-solid spherical or nearly spherical particles;

[0206] Furthermore, the non-solid spherical or nearly spherical particles include at least one of non-solid spherical or nearly spherical shell particles and non-solid spherical or nearly spherical shell particles with incomplete shells;

[0207] Furthermore, the spherical shell wall thickness of the non-solid spherical or nearly spherical shell-like particles is 2nm-10nm;

[0208] In the reaction system solution, when the nano sodium / potassium titanate or titanate film in situ endogenously doped with E-type elements is an intertwined agglomerate, the spheroidization and shrinkage process of a single film is interfered with by the spheroidization and shrinkage process of other intertwined films, and the free spheroidization process of "film-like → non-solid spherical shell-like → solid sphere-like" is restricted, so that multiple adjacent films merge and shrink into larger nano barium / lithium titanate non-free "spheroidization" units; multiple or a large number of non-free "spheroidization" units are further aggregated into larger agglomerates with a bonding strength between soft agglomeration and hard agglomeration; the agglomerates have structural characteristics similar to nanoporous structures, and the non-free "spheroidization" units are similar to ligaments in nanoporous structures.

[0209] When the above-mentioned non-spherical intermediate powder product is mainly a nanoporous sodium / potassium titanate or an irregular titanate powder intermediate product in situ endogenously doped with E-type elements, its primary "spheroidization" process and mechanism are as follows:

[0210] Although the nanoporous sodium / potassium titanate or irregular titanate powder particles doped in situ with E-type elements are generally large, their interiors are three-dimensional continuous network nanoporous structures. The average diameter of the ligaments in the nanoporous sodium / potassium titanate or titanate microstructure is less than 10nm, or even less than 5nm, and they have an extremely high specific surface area. Therefore, when the porous ligaments in the nanoporous sodium / potassium titanate or irregular titanate powder intermediate product are replaced by nanobarium / lithium titanate, a large number of ligaments can also undergo a shrinkage "spheroidization" process. Multiple nanoporous ligaments in adjacent positions can shrink and spheroidize into larger nanobarium / lithium titanate non-free "spheroidized" units. Multiple or a large number of non-free "spheroidized" units further aggregate into larger agglomerates with a bonding strength between soft agglomeration and hard agglomeration. The agglomerates have structural characteristics similar to nanoporous structures, and the non-free "spheroidized" units are similar to the ligaments in the nanoporous structure.

[0211] When the above-mentioned non-spherical intermediate powder product is mainly a nano-sodium / potassium titanate or titanate tube (rod) intermediate product in situ endogenously doped with E-type elements, its primary "spheroidization" process and mechanism are as follows:

[0212] In the reaction system solution, when the nano-sodium / potassium titanate or titanate tube (rod) in situ endogenously doped with an E-type element is a single free tube (rod), the nano-sodium / potassium titanate or titanic acid is replaced by nano-barium / lithium titanate, and thereafter, a spheroidization and shrinkage process of the tube (rod) occurs, turning it into a single spherical or nearly spherical particle; due to the limited size and volume of the original single tube (rod), the particle size of the single spherical or nearly spherical particle generally does not exceed 30 nm; further, depending on the size of the original tube (rod), the particle size of the single spherical or nearly spherical particle ranges from 3 nm to 30 nm; further, the particle size of the single spherical or nearly spherical particle ranges from 3 nm to 20 nm;

[0213] In the reaction system solution, when the nano sodium / potassium titanate or titanate tubes (rods) in situ endogenously doped with E-type elements are intertwined and clustered together, the spheroidization and shrinkage process of a single tube (rod) is interfered with by the spheroidization and shrinkage process of other intertwined tubes (rods), causing multiple adjacent tubes (rods) to merge and shrink into larger nano barium / lithium titanate non-free "spheroidization" units; multiple or a large number of non-free "spheroidization" units are further aggregated into larger agglomerates with a bonding strength between soft agglomeration and hard agglomeration; the agglomerates have structural characteristics similar to nanoporous structures, and the non-free "spheroidization" units are similar to ligaments in the nanoporous structure.

[0214] For the primary "spheroidization" process and mechanism of the above three different non-spherical intermediate powder products:

[0215] Furthermore, the components of the non-free "spheroidized" unit are mainly nano-barium titanate / lithium in situ endogenously doped with E-type elements;

[0216] Furthermore, the shape of the nano-barium titanate / lithium non-free "spherical" unit is between a non-completely solid sphere and a short rod. It can be understood that due to the influence of entanglement between different films or different tubes (rods) during the formation of the nano-barium titanate / lithium non-free "spherical" unit, the sphericity is affected, resulting in a shape between a sphere and a short rod.

[0217] Furthermore, the nano-barium titanate / lithium non-free "spheroidized" unit is in a metastable state;

[0218] Furthermore, the average diameter range of the in-situ endogenously doped E-type element nano-barium titanate / lithium non-free "spheroidized" unit is 5nm-300nm; further, the average diameter range of the in-situ endogenously doped E-type element nano-barium titanate / lithium non-free "spheroidized" unit is 5nm-250nm; the average diameter range of the in-situ endogenously doped E-type element nano-barium titanate / lithium non-free "spheroidized" unit is 5nm-200nm; the average diameter range of the in-situ endogenously doped E-type element nano-barium titanate / lithium non-free "spheroidized" unit is 5nm-100nm;

[0219] Further, the average particle size of the agglomerates is in the range of 50 nm to 5 μm; further, the average particle size of the agglomerates is in the range of 50 nm to 2 μm; further, the average particle size of the agglomerates is in the range of 50 nm to 1 μm;

[0220] Furthermore, the agglomerates can be subsequently dispersed by mechanical crushing and dispersion treatment to obtain nano-barium titanate / lithium spherical or nearly spherical powder products with the original nano-barium titanate / lithium non-free "spherical" units as basic particle units and in-situ endogenously doped with E-type elements;

[0221] Furthermore, the minimum sintering film-forming temperature of the nano-barium titanate / lithium spherical or nearly spherical powder product in situ endogenously doped with E-type elements using the original nano-barium titanate / lithium non-free "spherical" unit as the basic particle unit does not exceed 950°C;

[0222] Furthermore, the minimum sintering film-forming temperature of the nano-barium titanate / lithium spherical or nearly spherical powder product in situ endogenously doped with E-type elements using the original nano-barium titanate / lithium non-free "spherical" unit as the basic particle unit does not exceed 850°C;

[0223] Because the particle size of the non-free "spheroidized" units of nano-barium titanate / lithium is small, and most of them are not completely solid spheroidized, the specific surface area is still high, and they have metastable characteristics and high energy. Therefore, the minimum sintering temperature for the local melting of particles to form a film is low;

[0224] The three typical non-spherical intermediate powder products mentioned above undergo primary "spheroidization" during the cation exchange reaction. When the cation exchange reaction is completed but the primary "spheroidization" is insufficient, the solution temperature / pressure, the NaOH / KOH concentration in the solution, the reaction time, or the further dry heat treatment of the primary "spheroidization" product can be increased to obtain a spherical or nearly spherical nano-barium titanate / lithium particle powder product with more sufficient spheroidization and in-situ endogenous doping of E-type elements.

[0225] Furthermore, when the primary "spheroidization" in step 3 is insufficient, the degree of "spheroidization" can be improved by at least one of the following three methods:

[0226] (1) placing the reaction system in a sealed container and subjecting it to high temperature and high pressure treatment for a period of time, so that the non-free "spheroidized" units can be further shrunk into spherical or nearly spherical nano-barium titanate / lithium particles with a higher degree of solidity and in-situ endogenous doping with E-type elements; the temperature is 150° C. to 300° C., and the pressure is the pressure in the sealed container at this temperature;

[0227] (2) The solution in the reaction system is continuously evaporated to dryness, and then the remaining solid matter is heated to 150°C-400°C without changing the reaction container and kept warm for a period of time. Treatment at this temperature can further shrink the non-free "spheroidized" units into spherical or nearly spherical nano-barium titanate / lithium particles with a higher degree of solidity and in-situ endogenous doping of E-type elements;

[0228] (3) Collect the solid matter in the reaction system, heat it to 150℃-1300℃ and keep it warm for a period of time; treatment at this temperature, especially high temperature treatment (600℃-1300℃), can make the non-free "spheroidized" units further shrink into spherical or nearly spherical particles with a very high degree of solidity; however, during the high temperature treatment (600℃-1300℃), the non-free "spheroidized" units first shrink into spherical or nearly spherical nano-barium titanate / lithium particles with a very high degree of solidity. After they are almost completely solid, further high temperature treatment will cause the spherical or nearly spherical particles with a very high degree of solidity to sinter and agglomerate. Therefore, it is necessary to control the heat treatment temperature and time to obtain spherical or nearly spherical nano-barium titanate / lithium particles that are in situ endogenously doped with E-type elements and do not undergo obvious sintering and agglomeration.

[0229] Furthermore, after the above treatment, the spherical or nearly spherical nano-barium titanate / lithium particles can be dispersed by mechanical crushing and dispersion treatment to obtain a fully solid nano-barium titanate / lithium spherical or nearly spherical powder product in situ endogenously doped with E-type elements;

[0230] Furthermore, in the process of the in-situ endogenously doped nano sodium / potassium titanate or titanate matrix being converted into a nano barium titanate / lithium matrix through reaction, because the in-situ endogenously doped E-type elements are always in the solid matter before and after the reaction, the E-type elements cannot be discharged. Therefore, the E-type elements are still in-situ endogenously doped in the newly generated nano barium titanate / lithium matrix, thereby obtaining nano barium titanate / lithium particles in-situ endogenously doped with E-type elements.

[0231] Furthermore, when the E-type elements mainly include at least one of Au, Pt, Pd, Ru, Rh, Re, Os, and Ir, and:

[0232] 0.03 <C E / C Ti When ≤0.30, the E-type elements are mainly embedded in the barium titanate / lithium powder product in situ in the form of E nanoparticles; and the particle size of the E nanoparticles is 2nm-20nm;

[0233] 0.01 <C E / C Ti When the concentration is ≤0.03, the E-type elements are embedded in the barium titanate / lithium powder product in situ in the form of E nanoparticles and E atoms or atomic clusters;

[0234] 0 <C E / C Ti When ≤0.01, the E-type elements are mainly in situ endogenously doped into the barium titanate / lithium powder product in the form of E atoms or atomic clusters;

[0235] Furthermore, when the E-type elements mainly include at least one of Cu, Fe, Ni, and Co, and:

[0236] 0.05 <C E / C Ti When ≤0.30, the E-type elements are mainly embedded in the barium titanate / lithium powder product in situ in the form of E nanoparticles or oxidized E nanoparticles; and the particle size of the E nanoparticles is 2nm-20nm;

[0237] 0.02 <C E / C Ti When the concentration is ≤0.05, the E-type elements are in situ embedded in the barium titanate / lithium powder product in the form of E nanoparticles or oxidized E nanoparticles, as well as in the form of E atoms or atomic clusters;

[0238] 0 <C E / C Ti When ≤0.02, the E-type elements are mainly in-situ doped into the barium titanate / lithium powder product in the form of E atoms or atomic clusters;

[0239] Furthermore, when the E-type elements mainly include Ag, and:

[0240] 0.20 <C E / C Ti When ≤0.30, the E-type elements are mainly embedded in the barium titanate / lithium powder product in situ in the form of E nanoparticles; and the particle size of the E nanoparticles is 2nm-20nm;

[0241] 0.10 <C E / C Ti When ≤0.20, the E-type elements are in situ embedded in the barium titanate / lithium powder product in the form of E nanoparticles and E atoms or atomic clusters;

[0242] 0 <C E / C Ti When ≤0.10, the E-type elements are mainly in situ endogenously doped into the barium titanate / lithium powder product in the form of E atoms or atomic clusters;

[0243] Furthermore, when the E-type elements mainly include at least one of Zr and Hf, and:

[0244] 0 <C E / C Ti When ≤0.30, the E-type elements are mainly in-situ doped into the barium titanate / lithium powder product in the form of E atoms or atomic clusters;

[0245] As a preference, 0 <C E / C TiWhen ≤0.10, the E-type elements are mainly in situ endogenously doped into the barium titanate / lithium powder product in the form of E atoms or atomic clusters;

[0246] Because Ti, Zr and Hf are in the same group on the periodic table and have similar properties, Zr and Hf can be doped into barium titanate / lithium at a higher content;

[0247] Furthermore, when the E-type elements mainly include at least one of Cr, V, Nb, Ta, W, and Mo, and:

[0248] 0.20 <C E / C Ti When ≤0.30, the E-type elements are in situ embedded in the barium titanate / lithium powder product in the form of E nanoparticles or oxidized E nanoparticles, as well as in the form of E atoms or atomic clusters;

[0249] 0 <C E / C Ti When ≤0.20, the E-type elements are mainly in-situ doped into the barium titanate / lithium powder product in the form of E atoms or atomic clusters;

[0250] As a preference, 0 <C E / C Ti When ≤0.10, the E-type elements are mainly in situ endogenously doped into the barium titanate / lithium powder product in the form of E atoms or atomic clusters;

[0251] Because Ti has similar properties to Cr, V, Nb, Ta, W, and Mo, Cr, V, Nb, Ta, W, and Mo can be doped into barium titanate / lithium at a relatively high content;

[0252] Furthermore, when the E-type elements mainly include at least one of Mn, Sn, Pb, Bi, B, Be, and RE, and:

[0253] 0.10 <C E / C Ti When ≤0.30, the E-type elements are mainly embedded in the barium titanate / lithium powder product in situ in the form of E nanoparticles or oxidized E nanoparticles; and the particle size of the E nanoparticles is 2nm-20nm;

[0254] 0.06 <C E / C Ti When ≤0.10, the E-type elements are in situ embedded in the barium titanate / lithium powder product in the form of E nanoparticles or oxidized E nanoparticles, as well as in the form of E atoms or atomic clusters;

[0255] 0 <C E / C TiWhen ≤0.06, the E-type elements are mainly in situ endogenously doped into the barium titanate / lithium powder product in the form of E atoms or atomic clusters;

[0256] As a preference, 0 <C E / C Ti When ≤0.03, the E-type elements are mainly in situ endogenously doped into the barium titanate / lithium powder product in the form of E atoms or atomic clusters.

[0257] Description: When C E / C Ti =0, the content of doped E-type elements is 0, and the prepared product is barium titanate / lithium powder.

[0258] In particular, as an optimized wet one-pot process, when the intermediate powder product obtained in step 2 mainly comprises nano sodium / potassium titanate in situ endogenously doped with E-type elements, step 2 and step 3 can be combined to achieve the preparation of nano barium / lithium titanate particle powder products in situ endogenously doped with E-type elements through a one-pot process.

[0259] The one-pot solution combining steps 2 and 3 includes two methods:

[0260] The first method: Based on the completion of step 2, 2+ / Li + Barium / lithium source materials or materials containing Ba 2+ / Li + The barium / lithium source solution is added to the reaction system in step 2, and the reaction is continued at a certain temperature for a period of time;

[0261] For the specific information about step 2, please refer to the detailed description of step 2 above;

[0262] Further, the barium / lithium source material comprises at least one of Ba(OH)2, LiOH, BaCl2, LiCl, Ba(NO3)2, LiNO3, and Li2SO4;

[0263] Furthermore, the barium / lithium source material comprises at least one of Ba(OH)2 and LiOH;

[0264] Furthermore, in the reaction system after the barium / lithium source material is added, the Ba 2+ / Li + The total molar content C Ba / Li The molar content of Ti in nano sodium / potassium titanate or titanate powder is C Ti The ratio C Ba / Li / C Ti Satisfy 0.8≤C Ba / Li / C Ti ;

[0265] Furthermore, 1≤C Ba / Li / C Ti ; Further, 1≤C Ba / Li / C Ti ≤10;

[0266] Further, the reaction temperature is continued to be 50℃-T f溶液介质 ;

[0267] Further, the reaction temperature is continued to be 80℃-T f溶液介质 ; Further, the reaction temperature is continued to be 100 ℃ -T f溶液介 质 ;

[0268] Further, the continued reaction time is 10s-10h; further, the continued reaction time is 10s-1h;

[0269] Furthermore, when the reaction temperature is T f溶液介质 When the reaction time is 10s-15min;

[0270] Furthermore, when the reaction temperature is T f溶液介质 When the reaction time is 10s-5min;

[0271] Furthermore, when the reaction temperature is T f溶液介质 When the reaction time is 10s-2min;

[0272] In this reaction system, the solution contains enough NaOH / KOH components, so the reaction effect is good;

[0273] The second method: At the beginning of step 2, add an appropriate amount of Ba 2+ / Li + The barium / lithium source material is added to the reaction solution system together with NaOH / KOH, and then reacted at a certain temperature for a period of time.

[0274] The present application has found that during the hydrogen evolution and de-Ti reaction of the initial alloy in step 2, when the alkaline solution is mainly composed of Ba(OH)2 or (and) LiOH, under normal pressure, even if the concentration of the Ba(OH)2 or (and) LiOH solution reaches the highest concentration at its boiling point (more than 10 mol / L) and the temperature reaches the boiling point of the solution (105°C-130°C), the initial alloy is still difficult to undergo hydrogen evolution and de-Ti reaction with the Ba(OH)2 or (and) LiOH solution, and it almost remains in the original alloy state; therefore, nano-barium titanate / lithium titanate cannot be prepared directly by hydrogen evolution and de-Ti by the reaction of the initial alloy with the Ba(OH)2 or (and) LiOH solution, but requires a reaction involving NaOH / KOH, and barium titanate / lithium titanate can be prepared according to the path of "initial alloy → sodium / potassium titanate → barium / lithium titanate".

[0275] Therefore, in the second one-pot method, the reaction solution system needs to have sufficient effective concentration of NaOH / KOH to first realize the transformation of the initial alloy to sodium / potassium titanate; at the same time, in the reaction solution system, Ba 2+ / Li + The concentration of can not be too high, to ensure the conversion of sodium titanate / potassium → barium titanate / lithium, the right amount is good, otherwise too high a concentration of Ba 2+ / Li + It will affect the transformation of the initial alloy → sodium / potassium titanate and will also cause excessive Ba 2+ / Li + of waste.

[0276] Further, the barium / lithium source material comprises at least one of Ba(OH)2, LiOH, BaCl2, LiCl, Ba(NO3)2, LiNO3, and Li2SO4;

[0277] Specifically, in the alkaline solution,

[0278] When the total concentration of NaOH / KOH is in the range of 5mol / L-7.5mol / L, Ba 2+ / Li + The total corresponding concentration is no more than 2.0 mol / L;

[0279] When the total concentration of NaOH / KOH is in the range of 7.5mol / L-10mol / L, Ba 2+ / Li + The total corresponding concentration is no more than 3.5 mol / L;

[0280] When the total concentration of NaOH / KOH is in the range of 10mol / L-15mol / L, Ba 2+ / Li + The total corresponding concentration is no more than 5 mol / L;

[0281] When the total concentration of NaOH / KOH is in the range of 15mol / L-30mol / L, Ba 2+ / Li + The total concentration shall not exceed 8 mol / L;

[0282] Furthermore, in order to better achieve the transformation of "initial alloy → sodium / potassium titanate → barium / lithium titanate", the total concentration of NaOH / KOH in the one-pot alkaline solution ranges from 5 mol / L to 30 mol / L, preferably from 7 mol / L to 15 mol / L, and Ba 2+ / Li + The concentration of is as low as possible while ensuring the complete transformation of sodium / potassium titanate → barium / lithium titanate; its specific value can be determined according to the Ti content in the initial alloy in the reaction system;

[0283] Furthermore, the Ba-containing 2+ / Li + After the barium / lithium source material is added to the reaction system, the Ba 2+ / Li + The total molar content C Ba / Li The molar content of Ti in the initial alloy is C Ti The ratio C Ba / Li / C Ti Satisfy 0.8≤C Ba / Li / C Ti ;

[0284] Furthermore, 1≤C Ba / Li / C Ti ; Further, 1≤C Ba / Li / C Ti ≤1.5; further, 1≤C Ba / Li / C Ti ≤3;

[0285] Furthermore, 1≤C Ba / Li / C Ti ≤10;

[0286] For the specific information about step 2, please refer to the detailed description of step 2 above. For example, according to the specific reaction conditions 1)-4) of step 2 above, different morphologies of sodium / potassium titanate intermediate powder products are obtained:

[0287] 1) Under normal pressure, when the concentration of NaOH / KOH is high and the temperature of the alkaline solution is high, the intermediate powder product mainly includes nano-sodium / potassium titanate thin film powder in situ endogenously doped with E-type elements;

[0288] 2) Under normal pressure, when the concentration of NaOH / KOH is low and the temperature of the alkaline solution is low, the intermediate powder product mainly includes irregular nanoporous sodium / potassium titanate powders in situ endogenously doped with E-type elements;

[0289] 3) Under normal pressure, at a medium concentration of NaOH / KOH and a medium temperature of the alkaline solution, the intermediate powder products mainly include irregular nanoporous sodium / potassium titanate powders in situ endogenously doped with E-type elements and nano sodium / potassium titanate thin film powders in situ endogenously doped with E-type elements;

[0290] 4) The reaction is carried out in a closed container at a pressure higher than normal, with a high concentration of NaOH / KOH and a temperature higher than the boiling point T at one atmosphere. f溶液 At temperature, the intermediate powder products mainly include nano-sodium / potassium titanate tubes (rods) in situ endogenously doped with E-type elements;

[0291] The one-pot method:

[0292] Furthermore, the reaction temperature is 50°C-T f溶液介质 ;

[0293] Furthermore, the reaction temperature is 80°C-T f溶液介质 ; Further, the reaction temperature is 100 ℃ -T f溶液介质 ;

[0294] Further, the reaction time is 10s-10h; further, the reaction time is 10s-1h;

[0295] Furthermore, when the reaction temperature is T f溶液介质 When, the reaction time is 10s-15min;

[0296] Furthermore, when the reaction temperature is T f溶液介质 When, the reaction time is 10s-5min;

[0297] Furthermore, when the reaction temperature is T f溶液介质 When, the reaction time is 10s-2min;

[0298] In this reaction system, when the solution contains enough NaOH / KOH components and the C Ba / Li When the content is not high, the reaction effect is good;

[0299] Furthermore, in order to reduce the particle size of the nano-barium titanate / lithium particle powder product in situ endogenously doped with E-type elements, at least one of the following three methods can be used:

[0300] Method 1: During the reaction process of step 2 or (and) step 3, ultrasonic treatment is simultaneously applied to the reaction system; further, the frequency of the ultrasound is 20 kHz to 106 kHz; the ultrasonic treatment can fragment the particle size of the intermediate powder product to a certain extent, especially when the intermediate product is an irregular nanoporous sodium / potassium titanate powder in situ endogenously doped with an E-type element;

[0301] The second method is to perform mechanical crushing and dispersion after step 3, wherein the mechanical crushing and dispersion treatment includes at least one of ball milling and sand milling;

[0302] Furthermore, by mechanically dispersing the product, the agglomerated nano-barium titanate / lithium particles in situ endogenously doped with E-type elements can be further dispersed into finer particles.

[0303] Furthermore, after mechanical dispersion treatment of the product, the average particle size of the nano-barium titanate / lithium particles in situ endogenously doped with E-type elements ranges from 10nm to 250nm;

[0304] The third method is to perform mechanical crushing and dispersion treatment on the intermediate powder product after step 2, wherein the mechanical crushing and dispersion treatment method includes at least one of ball milling and sand milling;

[0305] The non-spherical intermediate powder product after step 2 is mainly at least one of nano sodium titanate / potassium thin film powder in situ endogenously doped with E-type elements, nano porous sodium / potassium irregular powder in situ endogenously doped with E-type elements, and nano sodium / potassium tubes (rods) in situ endogenously doped with E-type elements; it can be seen that compared with the mechanical dispersion treatment of spherical or nearly spherical nano barium / lithium titanate products by the second method, the third method has a better restricted crushing state in the crushing process of non-spherical nano sodium / potassium thin films, nano porous sodium / potassium irregular powders, and nano sodium / potassium tubes (rods), which can achieve a more obvious crushing and dispersion effect.

[0306] For the intermediate powder products of nano sodium / potassium titanate thin films, their thickness is generally less than 5nm and their average area is greater than 500nm. 2 Therefore, sand milling or ball milling can easily break up a single film and significantly reduce its average area, such as reducing the average area of ​​a single film to 1 / 10 of that before treatment, or even lower. This allows the particle size of the non-solid spherical or near-spherical shell particles obtained in the subsequent "spheroidization" process in step three to be as low as 5nm-50nm, or even lower; and the particle size of the nearly solid spherical or near-spherical particles that are further transformed through condensation treatment can be as low as 2nm-10nm, or even lower;

[0307] The area of ​​a single film is greatly reduced, and the size of the non-free "spherical" unit formed by the merger and contraction of several adjacent smaller films is also greatly reduced; therefore, after sand milling or ball milling, the average diameter of the spherical or nearly spherical nano-barium titanate / lithium particles in situ doped with E-type elements obtained in step three can be as low as 5nm-150nm, or even lower;

[0308] Furthermore, after sand milling or ball milling, the average diameter of the spherical or nearly spherical nano-barium titanate / lithium particles in situ doped with E-type elements obtained in step 3 can be reduced to 5 nm-100 nm, or even lower;

[0309] The same mechanism also applies to the nanoporous sodium / potassium titanate irregular powder intermediate product, so that after sand milling or ball milling, the average diameter of the spherical or nearly spherical nano-barium titanate / lithium particles in situ doped with E-type elements obtained in step three can be as low as 5nm-150nm, or even lower;

[0310] Furthermore, after sand milling or ball milling, the average diameter of the spherical or nearly spherical nano-barium titanate / lithium particles in situ doped with E-type elements obtained in step 3 can be as low as 5 nm to 100 nm, or even lower;

[0311] The same mechanism also applies to the intermediate powder product of the nano sodium / potassium titanate tube (rod), so that after sand milling or ball milling, the average diameter of the spherical or nearly spherical nano barium / lithium titanate particles in situ doped with E-type elements obtained in step three can be as low as 5nm-120nm, or even lower;

[0312] Furthermore, after sand milling or ball milling, the average diameter of the spherical or nearly spherical nano-barium titanate / lithium particles in situ doped with E-type elements obtained in step 3 can be as low as 5 nm to 80 nm, or even lower;

[0313] In actual operation, in order to obtain the finest possible nano-barium titanate / lithium particle powder product in situ endogenously doped with E-type elements, the above three methods can be used simultaneously in actual operation.

[0314] On the second aspect, the present application also relates to the application of nano barium titanate / lithium powder materials in situ endogenously doped with E-type elements prepared by the preparation method described in the first aspect in the fields of electronic ceramics, composite materials, coatings, powder metallurgy, multilayer ceramic capacitors, thermistors, piezoelectric ceramics, and battery materials.

[0315] Furthermore, the nano-barium titanate / lithium powder in situ endogenously doped with E-type elements can be used as a formula powder for multilayer ceramic capacitors (MLCCs); the nano-lithium titanate powder in situ endogenously doped with E-type elements can be used in the fields of lithium-ion batteries and asymmetric supercapacitors.

[0316] The beneficial effects of the solution described in this application are mainly reflected in the following aspects:

[0317] First, a novel doping method achieves in-situ endogenous doping of doping elements in nano-barium titanate / lithium particle powders. Currently, the main effective methods for preparing doped barium titanate particles are hydrothermal and sol-gel methods. Both methods first form a gel or suspension containing a barium titanate precursor, then add the doping substance during this period, and then perform hydrothermal treatment or sintering to obtain the doped barium titanate. This two-step doping process has certain characteristics of external doping, and in many cases it is difficult to achieve uniform doping effects at the atomic scale. This application, however, invents a completely new doping strategy. By uniformly dispersing the doping E-type element at the atomic scale in a T-Ti(E) intermetallic compound containing a solid solution of the E-type element or a T-Ti-E intermetallic compound containing the E-type element, the in-situ endogenous doping of the E-type element in the E-type intermetallic compound is obtained through hydrogen evolution and de-T reaction of these E-type intermetallic compounds. Furthermore, through cation replacement, the in-situ endogenous doping of the E-type element in the barium titanate / lithium nanoparticles is obtained. As can be seen, the E-type elements are present in the solid intermetallic compound, nano-sodium / potassium titanate, and nano-barium / lithium titanate, sequentially. They remain in the solid state and cannot be easily expelled from these solid materials. Therefore, the E-type elements continue to be in situ endogenously doped into the newly formed nano-barium titanate / lithium matrix, resulting in nano-barium titanate / lithium particles endogenously doped with the E-type elements. Depending on the E-type element doping content, two basic doping methods can be achieved: in situ endogenous doping with E atoms or atomic clusters, and in situ endogenous doping with E nanoparticles or oxidized E nanoparticles. The core of this doping strategy is to first prepare a T-Ti(E) intermetallic compound or a T-Ti-E intermetallic compound containing an E-type element in a solid solution with a certain E-type element content. Generally speaking, according to the alloy phase diagram, different E-type element atoms have different thermodynamic equilibrium solid solubilities in the T-Ti(E) intermetallic compound. When the thermodynamic equilibrium solid solubility of the E-type elements in the T-Ti intermetallic compound is very low, it is still possible to obtain a non-equilibrium solidified initial alloy through kinetic factors, that is, through rapid solidification of the melt. The E-type elements do not have time to be discharged from the T-Ti intermetallic compound in time during the rapid solidification process, thereby obtaining a T-Ti(E) non-equilibrium intermetallic compound with significantly improved solid solubility. Therefore, as long as the cooling rate is high enough, even if the equilibrium solid solubility is extremely low, theoretically most doping elements can be significantly dissolved in the T-Ti intermetallic compound, and based on this, the corresponding doped nano-barium / lithium titanate can be prepared by the method of the present application.

[0318] Secondly, the spheroidization mechanism of the process of obtaining nano-barium titanate / lithium through replacement reaction of sodium / potassium titanate or titanic acid was discovered and utilized, and nano-barium titanate / lithium spherical or near-spherical powder products with in-situ endogenous doping of E-type elements were prepared through non-spherical intermediate powders. Originally, the hydrogen evolution and de-T reaction of T-Ti(E) intermetallic compounds or T-Ti-E intermetallic compounds containing E-type elements obtained at least one of thin film powders, irregular nanoporous powders, and tubular (rod) powders, which do not have spherical or near-spherical characteristics and their applications are greatly limited. However, the present application cleverly uses non-spherical sodium / potassium titanate or titanic acid intermediate powders as the basis and utilizes this novel law to obtain spherical or near-spherical nano-barium titanate / lithium products, which are of great application significance.

[0319] Third, the present application can obtain nano-barium titanate / lithium spherical or nearly spherical powder products with extremely fine particle size that are in situ endogenously doped with E-type elements. Since the basic unit sizes (such as film thickness, porous band diameter) of sodium / potassium titanate or titanate film powder, sodium / potassium titanate or titanate irregular nanoporous powder, sodium / potassium titanate or titanate tube (rod) powder are extremely low (less than 10nm), barium titanate / lithium powder with a particle size less than 30nm can be prepared using them as intermediate products. Even if the particle size of the non-free "spheroidized" unit increases due to agglomeration, by pre-milling and sand milling the three typical non-spherical intermediate powder products to reduce the particle size of the intermediate powder before spheroidization, the particle size of the non-free "spheroidized" unit after the replacement reaction can also be comprehensively reduced to less than 100nm, or even lower. For a single sodium / potassium titanate or titanate film, after physical fragmentation and then replacement treatment, it is even possible to obtain barium titanate / lithium powder with a particle size of less than 20 nm.

[0320] Fourth, nano-barium / lithium titanate in situ doped with E-type elements can be produced in various morphologies, including spherical or near-spherical powders. For example, due to the free spheroidization mechanism of "thin film → non-solid spherical shell → solid sphere," if spheroidization is insufficient, larger non-solid spherical or near-spherical shell particles can be obtained. Further spheroidization treatment (such as heat treatment) can further reduce the particle size to nearly solid spherical or near-spherical product particles.

[0321] Fifth, the reaction conditions are simple and mild (high temperature and high pressure are not necessary conditions), and are also suitable for large-scale low-cost preparation. Generally speaking, the product can be prepared in a solution atmosphere at 100℃-150℃ under normal pressure. Moreover, the initial alloy can be directly added to the solution containing NaOH / KOH, Ba 2+ / Li + The reaction is completed in a few minutes using a hot alkaline solution.

[0322] Sixth, the sintering film-forming temperature of the prepared nano-barium titanate / lithium spherical or near-spherical powder product with in-situ endogenous doping of E-type elements is low, making it easy to prepare MLCC devices later. Because the nano-barium titanate / lithium prepared in this application has a small particle size and can be controlled to be non-completely solid and spherical, it has a high specific surface area and has metastable characteristics and high energy. Therefore, the minimum sintering temperature required for partial melting to form a film is relatively low, which can be as low as 850°C-950°C. The traditional process uses nano-barium titanate powder for pressureless and hot pressing sintering at temperatures of 1250°C and 1050°C, respectively, and requires several hours of heat preservation. BRIEF DESCRIPTION OF THE DRAWINGS

[0323] FIG1 is a TEM morphology of the intermediate product of nano-sodium titanate thin film powder prepared in Example 1;

[0324] FIG2 is a low-magnification and high-magnification SEM morphology of the nano-barium titanate powder product obtained in Example 1;

[0325] FIG3 is the SEM morphology of the nano-barium titanate powder product obtained in Example 1 after being treated at 950° C.;

[0326] FIG4 is a SEM morphology of the nano-barium titanate powder product obtained in Example 3;

[0327] FIG5 is a SEM morphology of the barium titanate powder product in situ endogenously doped with Ag element prepared in Example 4;

[0328] FIG6 is a SEM morphology of the barium titanate powder product in situ endogenously doped with rare earth Nd element prepared in Example 5;

[0329] FIG7 shows the low-magnification and high-magnification SEM morphologies of the irregular coarse powder intermediate of nanoporous sodium titanate obtained in Example 8;

[0330] FIG8 is a SEM morphology of nano-barium titanate powder obtained after heat treatment at 300° C. in Example 10;

[0331] FIG9 is a SEM morphology of nano-barium titanate powder obtained after heat treatment at 900° C. in Example 10; DETAILED DESCRIPTION

[0332] Example 1

[0333] According to the nominal composition Ti 25 Al 75 Weigh the metal Ti and Al raw materials in the ratio of (atomic percentage) and smelt them to obtain a composition mainly composed of Ti 25 Al 75 the alloy melt is prepared by a copper roller strip-throwing rapid solidification method into an initial alloy having a thickness of ~ 20 μm in the form of a strip, which is mainly composed of TiAl3 intermetallic compounds.

[0334] Under normal pressure, 0.8g of the Ti 25 Al 75 The initial alloy strips were added to 110 ml of a 10 mol / L NaOH aqueous solution at its boiling point (about 119°C) and stirred continuously. 25 Al 75 During the reaction with concentrated alkaline solution, the initial alloy strips are nano-fragmented through violent hydrogen evolution and de-Al reaction, and at the same time, the shape and composition are reconstructed to form a nano-sodium titanate film powder intermediate product.

[0335] The hydrogen evolution and de-Al reaction was completed within 15 seconds. After 2 minutes, the thin film powder intermediate product mainly composed of nano-sodium titanate thin film was collected. Its TEM morphology is shown in Figure 1. It is mainly composed of nano-sodium titanate thin film with a thickness of less than 3nm and an average area of ​​more than 1000nm. 2 Composition of two-dimensional sodium titanate film;

[0336] After collecting the above-mentioned nano sodium titanate film powder intermediate product, it is not washed to retain the residual alkali;

[0337] Under normal pressure, the sodium titanate film powder intermediate product was added to 50 ml of boiling water. Under stirring, 3.5 g of Ba(OH)2·8H2O was dissolved in 10 ml of boiling water and added to the reaction system. During the reaction, the sodium titanate intermediate product was replaced by barium titanate, and the sodium titanate film underwent a spherical shape mutation. After 4 minutes of reaction, the solid product in the reaction system was collected to obtain a nano-barium titanate powder mainly composed of spherical or nearly spherical barium titanate particles with a powder particle size range of 5 nm to 150 nm. The SEM low-magnification and high-magnification morphologies are shown in Figure 2.

[0338] When the obtained nano-barium titanate powder is heat-treated at 950°C for 1 hour in a loose state, the powder is sintered and formed into a film, as shown in Figure 3. This shows that the obtained nano-barium titanate powder has excellent low-temperature sintering performance and has good application prospects in the field of electronic ceramics, such as multilayer chip ceramic capacitors.

[0339] Example 2

[0340] According to the steps of Example 1, a thin film powder intermediate product mainly composed of a nano-sodium titanate thin film is first obtained and collected;

[0341] After the nano-sodium titanate film powder intermediate product is collected, it is not washed to retain the residual alkali, and then it is sanded; because the film area is large, it can be easily broken into fragmented sodium titanate film fragments (such as an average area of ​​less than 500nm). 2 fragments) while improving its dispersibility.

[0342] The nano sodium titanate film powder intermediate product after sand milling and dispersion treatment is added to 100 ml of boiling water. Under stirring, 3.5 g of Ba(OH)2·8H2O is dissolved in 10 ml of boiling water and added to the reaction system. During the reaction, the sodium titanate film intermediate product is replaced by barium titanate, and the sodium titanate film undergoes a spherical shape mutation. After reacting for 5 minutes, the solid product in the reaction system is collected to obtain a nano barium titanate powder mainly composed of spherical or nearly spherical barium titanate particles. Since the intermediate product has been refined, the particle size of the obtained product ranges from 5 nm to 45 nm.

[0343] The spherical or nearly spherical nano-barium titanate powder with certain agglomeration characteristics is further subjected to sand milling and dispersion treatment to obtain spherical or nearly spherical ultrafine nano-barium titanate powder with excellent dispersibility, and the powder particle size range is 5nm-40nm.

[0344] Example 3

[0345] According to the nominal composition Ti 25 Al 75 Weigh the metal Ti and Al raw materials in the ratio of (atomic percentage) and smelt them to obtain a composition mainly composed of Ti 25 Al 75 the alloy melt is prepared by a copper roller strip-throwing rapid solidification method into an initial alloy having a thickness of ~ 20 μm in the form of a strip, which is mainly composed of TiAl3 intermetallic compounds.

[0346] Prepare 110 ml of 10 mol / L NaOH aqueous solution, then dissolve 3.5 g of Ba(OH)2·8H2O in the NaOH aqueous solution. Heat the alkaline solution to its boiling point under normal pressure, then add 0.8 g of Ti 25 Al 75 The initial alloy strips are added to an alkaline solution for reaction.

[0347] The hydrogen evolution de-Al reaction was completed within 30 s. During the reaction, the initial alloy strips were first transformed into sodium titanate film intermediates through hydrogen evolution de-Ti, and then immediately further replaced by barium titanate. At the same time, the sodium titanate film intermediates underwent a spherical shape mutation.

[0348] 3.5 minutes after the start of the hydrogen evolution and de-Al reaction, the solid matter in the reaction system was collected, and a nano-barium titanate powder mainly composed of spherical or nearly spherical barium titanate particles was obtained, and its SEM morphology is shown in Figure 4. As can be seen from the figure, its morphology mainly includes two types: one is the agglomeration of fine particles, and the particle size of each fine nanoporous "tie" unit (non-free "spherical" unit) ranges from 5nm to 60nm. These small units agglomerate to form agglomerates with a particle size of about 1μm. The agglomerated powder particles of this morphology may be related to the entangled and agglomerated sodium titanate film intermediate product; the other is incomplete hollow spherical shell particles with an outer diameter of 10nm-120nm and a shell thickness of less than 10nm; each single hollow spherical shell particle may have evolved from the reaction of a sodium titanate film intermediate product.

[0349] When the obtained nano-barium titanate powder is heat-treated at 850°C for 4 hours in a compacted state, the powder is sintered and formed into a film, indicating that the obtained nano-barium titanate powder has excellent low-temperature sintering performance and has good application prospects in the field of electronic ceramics, such as multilayer chip ceramic capacitors.

[0350] Example 4

[0351] According to Ag1Ti 24.75 Al 74.25 The metal Ag, Ti and Al raw materials are weighed in the ratio of (atomic percentage) and smelted to obtain Ag1Ti 24.75 Al 74.25 The alloy melt is prepared by a copper roller strip-spinning method to form an initial alloy having a thickness of ~20 μm, which is mainly composed of a TiAl3 (Ag) intermetallic compound containing a solid solution of Ag element.

[0352] Under normal pressure, 0.25g of the Ag1Ti 24.75 Al 74.25 The initial alloy strips were added to 50 ml of a 10 mol / L NaOH aqueous solution at its boiling point (about 119°C) and stirred continuously. 24.75 Al 74.25 During the reaction with concentrated alkaline solution, the initial alloy strips are nano-fragmented by the intense hydrogen evolution and de-Al reaction, and simultaneously undergo shape and composition reconstruction to generate a nano-sodium titanate thin film powder intermediate product that is in situ endogenously doped with Ag elements mainly in the form of atoms or atomic clusters.

[0353] The hydrogen evolution and de-Al reaction was completed within 15 seconds, and the temperature was kept at room temperature for 3 minutes to ensure that the reaction was completely completed. Then, 1g of Ba(OH)2·8H2O was dissolved in 5ml of boiling water under stirring and added to the reaction system. During the reaction, the intermediate product of the sodium titanate film in situ endogenously doped with Ag element was replaced by nano-barium titanate in situ endogenously doped with Ag element, and at the same time, the sodium titanate film matrix underwent a spherical shape mutation. After 3 minutes of mixing reaction, the solid product in the reaction system was collected, and a powder mainly composed of spherical or nearly spherical nano-barium titanate particles in situ endogenously doped with Ag element was obtained, and the particle size range was 5nm-150nm. The SEM photograph of the powder is shown in Figure 5.

[0354] The nano-barium titanate powder in situ endogenously doped with Ag element with certain agglomeration characteristics is subjected to sand milling and dispersion treatment to obtain the nano-barium titanate powder in situ endogenously doped with Ag element with excellent dispersibility, and the powder particle size range is 5nm-140nm.

[0355] Example 5

[0356] According to Nd 0.2 Ti 24.8 Al 75 Ti with rare earth Nd solid solution was weighed in the ratio of (atomic percentage) 99.5 Nd 0.5 , Ti and Al raw materials, smelting to obtain the main components of Nd 0.2 Ti 24.8 Al 75 the alloy melt is prepared by a copper roller strip-throwing rapid solidification method into an initial alloy having a thickness of ~20 μm in the form of a strip, which is mainly composed of a TiAl3 (Nd) intermetallic compound containing a solid solution of Nd element.

[0357] Under normal pressure, 0.25g of the Nd 0.2 Ti 24.8 Al 75 The initial alloy strip was added to 50 ml of a 10 mol / L NaOH aqueous solution at its boiling point (about 119°C) and stirred continuously. 0.2 Ti 24.8 Al 75 During the reaction with concentrated alkaline solution, the initial alloy strips are nano-fragmented by the intense hydrogen evolution and de-Al reaction, and simultaneously undergo shape and composition reconstruction to generate a nano-sodium titanate thin film powder intermediate product that is in situ endogenously doped with Nd elements mainly in the form of atoms or atomic clusters.

[0358] The hydrogen evolution and de-Al reaction was completed within 15 seconds, and the temperature was kept for 3 minutes to ensure that the reaction was completely completed. Then, 1g of Ba(OH)2·8H2O was dissolved in 5ml of boiling water under stirring and added to the reaction system. During the reaction, the intermediate product of the sodium titanate film in situ endogenously doped with Nd element was replaced by nano-barium titanate in situ endogenously doped with Nd element, and at the same time, the sodium titanate film matrix underwent a spherical shape mutation. After 3 minutes of mixing reaction, the solid product in the reaction system was collected, and a powder mainly composed of spherical or nearly spherical nano-barium titanate particles in situ endogenously doped with Nd element was obtained, and the particle size range was 5nm-75nm. The SEM photograph of the powder is shown in Figure 6.

[0359] The nano-barium titanate powder in situ endogenously doped with Nd element with certain agglomeration characteristics is subjected to sand milling and dispersion treatment to obtain the nano-barium titanate powder in situ endogenously doped with Nd element with excellent dispersibility, and the powder particle size range is 5nm-60nm.

[0360] Example 6

[0361] According to Zr3Ti 22 Al 75 Weigh Zr, Ti and Al raw materials in the ratio of (atomic percentage) and smelt them to obtain Zr3Ti 22 Al 75 The alloy melt is prepared by a copper roller strip-spinning method to form an initial alloy having a thickness of 20 μm to 30 μm, which is mainly composed of a TiAl3 (Zr) intermetallic compound containing a solid solution of Zr element.

[0362] Under normal pressure, 0.25g of the above-prepared Zr3Ti 22 Al 75 The initial alloy strip was added into 50 ml of a 10 mol / L KOH aqueous solution at its boiling point (about 125°C) and stirred continuously. 22 Al 75 During the reaction with concentrated alkaline solution, the initial alloy strips are nano-fragmented by a violent hydrogen evolution and de-Al reaction, and simultaneously undergo shape and composition reconstruction to generate a nano-potassium titanate thin film powder intermediate product in situ endogenously doped with Zr in the form of major atoms or atomic clusters.

[0363] The hydrogen evolution and de-Al reaction is completed within 15 seconds, and the heat is maintained for 3 minutes to ensure that the reaction is completely completed. Then, 0.20g of LiCl is added to the reaction system under stirring. During the reaction, the intermediate product of the potassium titanate film in situ endogenously doped with Zr is replaced by nano-lithium titanate in situ endogenously doped with Zr, and at the same time, the potassium titanate film matrix undergoes a spherical shape mutation. After 3 minutes of mixing reaction, the solid product in the reaction system is collected, and a powder mainly composed of spherical or nearly spherical lithium titanate particles in situ endogenously doped with Zr is obtained, and the particle size range is 5nm-150nm.

[0364] Example 7

[0365] According to Au1Ti 23 Al 75 Weigh Au, Ti and Al raw materials in the ratio of (atomic percentage) and smelt them to obtain Au1Ti 23 Al 75 The alloy melt is prepared by a copper roller strip-spinning method to form an initial alloy having a thickness of 20 μm to 30 μm, which is mainly composed of a TiAl3 (Au) intermetallic compound in which Au element is dissolved.

[0366] Under normal pressure, 0.25g of the Au1Ti 23 Al 75 The initial alloy strip was added to 50 ml of a 10 mol / L NaOH aqueous solution at its boiling point (about 119°C) and stirred continuously. 23 Al 75 During the reaction with the concentrated alkaline solution, the initial alloy strips are nano-fragmented through a violent hydrogen evolution and de-Al reaction. Simultaneously, the shape and composition are reconstructed to form a nano-sodium titanate thin film powder intermediate product in which Au elements are in situ endogenously doped in the form of mainly Au nanoparticles. The Au nanoparticles have a particle size of 2nm-10nm.

[0367] The hydrogen evolution and de-Al reaction is completed within 15 seconds, and the heat is maintained for 3 minutes to ensure that the reaction is completely completed. Then, 1g of Ba(OH)2·8H2O is added to the reaction system under stirring. During the reaction, the intermediate product of the sodium titanate film in situ endogenously doped with Au nanoparticles is replaced by nano-lithium titanate in situ endogenously doped with Au nanoparticles, and at the same time, the sodium titanate film matrix undergoes a spherical shape mutation. After 3 minutes of mixing reaction, the solid product in the reaction system is collected, and a powder mainly composed of spherical or nearly spherical lithium titanate particles in situ endogenously doped with Au nanoparticles is obtained, the particle size range of which is 5nm-150nm, and the particle size of the doped Au nanoparticles is 2nm-10nm.

[0368] Example 8

[0369] According to the nominal composition Ti 25 Al 75 Weigh the metal Ti and Al raw materials in the ratio of (atomic percentage) and smelt them to obtain a composition mainly composed of Ti 25 Al 75 the alloy melt is prepared by a copper roller strip-throwing rapid solidification method into an initial alloy having a thickness of ~ 30 μm in the form of a strip, which is mainly composed of TiAl3 intermetallic compounds.

[0370] Under normal pressure, 0.25g of the Ti 25 Al 75 The initial alloy strips were reacted with 20 ml of 10 mol / L NaOH aqueous solution at 35°C for 2 h to obtain a preliminarily crushed nanoporous sodium titanate irregular coarse powder with a particle size of 0.1 μm-5 μm. The size of the porous bands inside the powder was less than 5 nm, as shown in Figure 7.

[0371] After collecting the above-mentioned nanoporous sodium titanate irregular coarse powder intermediate product, it is not washed to retain residual NaOH;

[0372] Under normal pressure, 2 g of Ba(OH)2·8H2O was added to 10 ml of water, and the solution was heated to its boiling point. Then, the irregular coarse powder of nanoporous sodium titanate was added to the solution under ultrasound and stirring. After reacting for 10 minutes, the solid powder was collected to obtain a nano-barium titanate powder mainly composed of spherical or nearly spherical barium titanate particles with a powder particle size range of 5 nm to 150 nm.

[0373] Example 9

[0374] According to Ti 25 Al 75 Weigh the metal Ti and Al raw materials in the ratio of (atomic percentage) and smelt them to obtain a composition of Ti 25 Al 75 The alloy melt is prepared into an initial alloy in the form of a strip with a thickness of 25 μm by a copper roller strip-spinning rapid solidification method, which is mainly composed of TiAl3 intermetallic compounds.

[0375] At room temperature and pressure, 0.5 g of the initial alloy strip prepared above and 50 mL of a 10 mol / L NaOH aqueous solution were placed in a sealed reactor lined with polytetrafluoroethylene. The sealed reactor and the initial alloy and NaOH aqueous solution were then immediately heated to 250°C over 10 minutes and then maintained at this temperature for 20 minutes. At this point, the pressure in the reactor was higher than atmospheric pressure.

[0376] After 20 minutes, the reactor was placed in cold water to rapidly cool down. After the reactor cooled to room temperature, the pressure inside the reactor was restored to normal pressure, and the solid matter in the reactor was separated from the solution to obtain the sodium titanate nanotube powder intermediate product, the outer diameter of which was 3nm to 12nm.

[0377] After collecting the sodium titanate nanotube powder intermediate product, it is not washed to retain the residual NaOH;

[0378] Under normal pressure, 4g of Ba(OH)2·8H2O was added to 20ml of water, and the solution was heated to its boiling point. Then, the sodium titanate nanotube powder intermediate product was added to the solution under ultrasonic and stirring conditions. After reacting for 10 minutes, the solid powder was collected to obtain nano-barium titanate powder mainly composed of spherical or nearly spherical barium titanate particles with a powder particle size range of 5nm-200nm.

[0379] Example 10

[0380] According to Ti 40 Al 60 Weigh the metal Ti and Al raw materials in the ratio of (atomic percentage) and smelt them to obtain a composition of Ti 40 Al 60 The alloy melt is prepared by a copper roller strip-throwing rapid solidification method into an initial alloy with a thickness of ~1mm in the form of a strip, which is mainly composed of TiAl2 intermetallic compounds and TiAl intermetallic compounds.

[0381] Under normal pressure, 0.25g of the Ti 40 Al 60 The initial alloy strips were added to 50 ml of a 15 mol / L KOH aqueous solution at its boiling point (about 150°C) and stirred continuously. 40 Al 60 The initial alloy strips are nano-fragmented by the intense hydrogen evolution and de-Al reaction during the reaction with the concentrated alkaline solution. At the same time, the shape and composition are reconstructed to obtain a nano-potassium titanate thin film powder material. The thickness of the single film is 0.25nm to 3nm, and the average area of ​​the film is greater than 1000nm. 2 .

[0382] The nano-potassium titanate film powder material separated from the alkaline solution is dispersed in water. Under stirring, 0.025 mol / L HCl solution is gradually added thereto to continuously reduce the pH value of the mixed solution and finally control the pH value of the mixed solution between 2 and 5. After 10 minutes, the mixture is separated, washed, and dried to obtain a nano-titanate film. The thickness of a single film is about 0.25 nm to 3 nm, and the average area of ​​a single film is greater than 1000 nm. 2 .

[0383] Under normal pressure, the titanate film powder intermediate product was added to 20 ml of boiling water. While stirring, 1 g of Ba(OH)2·8H2O was dissolved in 5 ml of boiling water and added to the reaction system. During the reaction, the titanate film intermediate product was replaced by barium titanate, and the titanate film slowly underwent a spherical shape transformation.

[0384] Path 1: The solution volume was maintained by adding water. After reacting for 20 minutes, the solid matter was collected and then heated to 300°C and kept warm for 5 minutes to further promote its spheroidization process. Nano-barium titanate powder mainly composed of spherical or nearly spherical barium titanate particles was obtained. The powder particle size ranged from 10 nm to 150 nm. The SEM morphology is shown in Figure 8.

[0385] Route 2: The solution volume was maintained by adding water. After reacting for 8 minutes, the solid material was collected and then heated to 900°C and kept warm for 1 minute to further promote its spheroidization process. Nano-barium titanate powder mainly composed of spherical or nearly spherical barium titanate particles was obtained. The powder particle size ranged from 10 nm to 300 nm, and its SEM morphology is shown in Figure 9. The nano-barium titanate powder with certain agglomeration characteristics was sand-milled and dispersed to obtain spherical or nearly spherical barium titanate powder with excellent dispersibility. The powder particle size ranged from 10 nm to 300 nm.

[0386] Example 11

[0387] According to the nominal composition Ti 25 Al 75 Weigh the metal Ti and Al raw materials in the ratio of (atomic percentage) and smelt them to obtain a composition mainly composed of Ti 25 Al 75 the alloy melt is prepared by a copper roller strip-throwing rapid solidification method into an initial alloy having a thickness of ~ 20 μm in the form of a strip, which is mainly composed of TiAl3 intermetallic compounds.

[0388] Under normal pressure, 0.8g of the Ti 25 Al 75 The initial alloy strips were added to 110 ml of a 10 mol / L NaOH aqueous solution at its boiling point (about 119°C) and stirred continuously. 25 Al 75 During the reaction with concentrated alkaline solution, the initial alloy strips are nano-fragmented through violent hydrogen evolution and de-Al reaction, and at the same time, the shape and composition are reconstructed to form a nano-sodium titanate film powder intermediate product.

[0389] The hydrogen evolution and de-Al reaction was completed within 15 seconds. After 2 minutes, the thin film powder intermediate product mainly composed of nano-sodium titanate film was collected. The thickness was less than 3nm and the average area was greater than 1000nm. 2 Composition of two-dimensional sodium titanate film;

[0390] The nano sodium titanate film powder intermediate product is sand-milled and mixed with BaCO3 powder, wherein Ba 2+ The ratio of the molar content of Ti to the molar content of Ti in the intermediate product of the nano sodium titanate film powder is about 1:1; the mixed powder is compacted and solid-phase reacted at 1000°C for 1 hour, and then crushed and dispersed by ball milling and sand milling to obtain a nano barium titanate particle powder product with a powder particle size range of 20nm-300nm.

[0391] Example 12

[0392] According to Ti 25 Zn 75 The ratio of (atomic percentage) is called metal Ti and Zn raw materials, and the composition is Ti 25 Zn 75 The alloy melt is prepared into an initial alloy in the form of a strip with a thickness of 30 μm by a copper roller strip-spinning method, which is mainly composed of TiZn3 intermetallic compounds.

[0393] Under normal pressure, 0.25g of the Ti 25 Zn 75 The initial alloy strips were added into 50 ml of a 15 mol / L KOH aqueous solution at 105°C to 115°C, and stirred continuously. 25 Zn 75 The initial alloy strips are nano-fragmented by the intense hydrogen evolution and Zn removal reaction during the reaction with the concentrated alkaline solution, and are simultaneously reconstructed in shape and composition to form nano-potassium titanate thin film materials. The thickness of the single film is 0.25nm to 3nm, and the average area of ​​the film is greater than 1000nm. 2 .

[0394] The hydrogen evolution and Zn removal reaction was completed within 30 seconds, and the reaction system was kept warm for another 3 minutes. Then, while stirring, 1g of Ba(OH)2·8H2O was dissolved in 5ml of boiling water and added to the reaction system. During the reaction, the potassium titanate intermediate product was replaced by barium titanate, and the potassium titanate film underwent a spherical shape mutation. After 40 seconds of mixing, the solid product in the reaction system was collected to obtain a nano-barium titanate powder composed primarily of spherical or nearly spherical barium titanate particles with a particle size range of 5nm to 80nm.

[0395] The spherical or nearly spherical nano-barium titanate powder with certain agglomeration characteristics is subjected to sand milling and dispersion treatment to obtain spherical or nearly spherical nano-barium titanate powder with excellent dispersibility, and the powder particle size range is 5nm-75nm.

[0396] The technical features of the above-mentioned embodiments can be combined arbitrarily. In order to make the description concise, not all possible combinations of the technical features in the above-mentioned embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0397] The above-described embodiments merely illustrate several implementations of the present invention, and while their descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the patent. It should be noted that a person skilled in the art would be able to make numerous variations and improvements without departing from the spirit of the present invention, all of which fall within the scope of protection of the present invention. Therefore, the scope of protection of the patent for this invention shall be determined by the appended claims.

Claims

1. A method for preparing doped nano-barium titanate / lithium powder, characterized in that: The method comprises the following steps: Step 1: preparing an initial alloy, wherein the initial alloy comprises a T element, a Ti element, and an E element, and the phase composition of the initial alloy comprises a T-Ti(E) intermetallic compound in which the E element is solid-dissolved or a T-Ti-E intermetallic compound containing the E element; wherein, in the T-Ti(E) intermetallic compound or the T-Ti-E intermetallic compound, the molar ratio of the E element to the Ti element is 0≤C E / C Ti ≤0.30; T-type elements include at least one of Al and Zn; E-type elements include at least one of Zr, Hf, Cr, V, Nb, Ta, W, Mo, Mn, Fe, Ni, Co, Sn, Pb, Bi, B, Be, Au, Pt, Pd, Ru, Rh, Re, Os, Ir, Ag, Cu, and RE; wherein RE includes at least one rare earth element; Step 2: The initial alloy undergoes a hydrogen evolution and de-tantalum reaction with an alkaline solution mainly composed of NaOH / KOH to obtain an intermediate powder product, which mainly comprises at least one of a nano sodium / potassium titanate thin film powder in situ endogenously doped with an E-type element, a nano porous sodium / potassium titanate irregular powder in situ endogenously doped with an E-type element, and a nano sodium / potassium titanate tube (rod) in situ endogenously doped with an E-type element; Alternatively, the intermediate powder product composed of the nano-sodium / potassium titanate in situ endogenously doped with E-type elements is reacted with a dilute acid to obtain a hydrogen ion-substituted nano-titanate intermediate powder product in situ endogenously doped with E-type elements, the intermediate powder product mainly comprising at least one of a nano-titanate thin film powder in situ endogenously doped with E-type elements, a nano-porous titanate irregular powder in situ endogenously doped with E-type elements, and a nano-titanate tube (rod) in situ endogenously doped with E-type elements; Step 3: Mix the intermediate powder product with Ba 2+ / Li + The barium / lithium source material reacts for a period of time under a specific temperature, pressure and medium atmosphere, causing the above-mentioned non-spherical intermediate powder product to undergo a cation replacement reaction and a "spheroidization" morphology change, thereby obtaining a spherical or nearly spherical nano-barium titanate / lithium particle powder product that is in situ endogenously doped with E-type elements.

2. The method for preparing doped nano-barium titanate / lithium powder according to claim 1, characterized in that: The initial alloy reacts with an alkaline solution mainly composed of NaOH / KOH, and different intermediate powder products are obtained under different reaction conditions: 1) Under normal pressure, when the concentration of NaOH / KOH is high and the temperature of the alkaline solution is high, the intermediate powder product mainly includes nano-sodium / potassium titanate thin film powder in situ endogenously doped with E-type elements; 2) Under normal pressure, when the concentration of NaOH / KOH is low and the temperature of the alkaline solution is low, the intermediate powder product mainly includes irregular nanoporous sodium / potassium titanate powders in situ endogenously doped with E-type elements; 3) Under normal pressure, at a medium concentration of NaOH / KOH and a medium temperature of the alkaline solution, the intermediate powder products mainly include irregular nanoporous sodium / potassium titanate powders in situ endogenously doped with E-type elements and nano sodium / potassium titanate thin film powders in situ endogenously doped with E-type elements; 4) The reaction is carried out in a closed container at a pressure higher than normal, with a high concentration of NaOH / KOH and a temperature higher than the boiling point T at one atmosphere. f溶液 At the temperature, the intermediate powder product mainly includes nano sodium / potassium titanate tubes (rods) in situ endogenously doped with E-type elements.

3. The method for preparing doped nano-barium titanate / lithium powder according to claim 1, characterized in that: The basic methods of in-situ endogenous doping of type E elements mainly include at least one of the following two methods: a) The E-type elements are in situ endogenously embedded in the sodium / potassium titanate or titanate intermediate powder product in the form of E nanoparticles or oxidized E nanoparticles; at this time, the E nanoparticles or oxidized E nanoparticles are in a different phase relative to the sodium / potassium titanate or titanate matrix; b) E-type elements are in situ endogenized in the sodium / potassium titanate or titanate intermediate powder product in the form of E atoms or atomic clusters; at this time, relative to the sodium / potassium titanate or titanate matrix, the E atoms or atomic clusters fail to form a different phase or fail to form an obvious different phase.

4. The method for preparing doped nano-barium titanate / lithium powder according to claim 1, characterized in that: The conditions for the "spheroidization" and cation replacement reaction of the non-spherical intermediate powder product are mainly as follows: the medium atmosphere is mainly a solution medium, the pressure is normal pressure or higher than normal pressure, the barium / lithium source material is mainly Ba 2+ / Li + The reaction temperature is 30℃-T f溶液介质 ; Among them, T f溶液介质 It is the boiling point of the solution medium at normal pressure.

5. The method for preparing doped nano-barium titanate / lithium powder according to claim 1, characterized in that: The average particle size of the nano-barium titanate / lithium particles in situ endogenously doped with E-type elements ranges from 5 nm to 300 nm.

6. The method for preparing doped nano-barium titanate / lithium powder according to claim 1, characterized in that: The Ba 2+ / Li + The barium / lithium source materials include Ba 2+ / Li + Alkali, containing Ba 2+ / Li + at least one of the salts of .

7. The method for preparing doped nano-barium titanate / lithium powder according to claim 1, characterized in that: When the medium atmosphere is non-solution, step three is specifically: mixing the intermediate powder product of step two with a Ba-containing 2+ / Li + The barium / lithium source materials are ball-milled and sand-milled to mix, and then solid-phase reaction is carried out; Among them, Ba in the reaction system 2+ / Li + The ratio of the molar content of to the molar content of Ti in the intermediate powder product is in the range of 0.75:1 to 1.25:1; after the reaction is completed, the mixture is crushed and dispersed by ball milling or sand milling to obtain a nano-barium titanate / lithium particle powder product in situ endogenously doped with E-type elements.

8. The method for preparing doped nano-barium titanate / lithium powder according to claim 1, characterized in that: When the primary "spheroidization" in step 3 is insufficient, improve the degree of "spheroidization" by at least one of the following three methods: (1) The reaction system is placed in a sealed container and treated with high temperature and high pressure for a period of time, so that the non-free "spheroidized" units can be further shrunk into spherical or nearly spherical nano-barium titanate / lithium particles with a higher degree of solidity and in-situ endogenous doping of E-type elements; (2) continuously evaporating the solution of the reaction system to dryness, and then continuing to heat the remaining solid matter to 150°C-400°C without changing the reaction container and keeping the temperature for a period of time; (3) Collect the solid matter in the reaction system, heat it to 150℃-1300℃ and keep it warm for a period of time.

9. The method for preparing doped nano-barium titanate / lithium powder according to claim 1, characterized in that: When the E-type elements mainly include at least one of Au, Pt, Pd, Ru, Rh, Re, Os, and Ir, and 0 <C E / C Ti When ≤0.01, the E-type elements are mainly in situ endogenously doped into the barium titanate / lithium powder product in the form of E atoms or atomic clusters; When the E-type elements mainly contain at least one of Cu, Fe, Ni, and Co, and 0 <C E / C Ti When ≤0.02, the E-type elements are mainly in-situ doped into the barium titanate / lithium powder product in the form of E atoms or atomic clusters; When the E-type elements mainly contain Ag, and 0 <C E / C Ti When ≤0.10, the E-type elements are mainly in situ endogenously doped into the barium titanate / lithium powder product in the form of E atoms or atomic clusters; When the E-type elements mainly contain at least one of Zr and Hf, and 0 <C E / C Ti When ≤0.30, the E-type elements are mainly in-situ doped into the barium titanate / lithium powder product in the form of E atoms or atomic clusters; When the E-type elements mainly contain at least one of Cr, V, Nb, Ta, W, and Mo, and 0 <C E / C Ti When ≤0.10, the E-type elements are mainly in situ endogenously doped into the barium titanate / lithium powder product in the form of E atoms or atomic clusters; When the E-type elements mainly include at least one of Mn, Sn, Pb, Bi, B, Be, and RE, and 0 <C E / C Ti When ≤0.06, the E-type elements are mainly in situ endogenously doped into the barium titanate / lithium powder product in the form of E atoms or atomic clusters.

10. The method for preparing doped nano-barium titanate / lithium powder according to claim 1, characterized in that: Step 2 is combined with step 3 to prepare nano-barium titanate / lithium particle powder products in situ endogenously doped with E-type elements through a one-pot method.

11. The method for preparing doped nano-barium titanate / lithium powder according to claim 10, characterized in that: The one-pot solution combining steps 2 and 3 includes two methods: The first method: Based on the completion of step 2, 2+ / Li + Barium / lithium source materials or materials containing Ba 2+ / Li + The barium / lithium source solution is added to the reaction system in step 2, and the reaction is continued at a certain temperature for a period of time; The second method: At the beginning of step 2, add an appropriate amount of Ba 2+ / Li + The barium / lithium source material is added to the reaction solution system together with NaOH / KOH, and then reacted at a certain temperature for a period of time.

12. The method for preparing doped nano-barium titanate / lithium powder according to claim 1, characterized in that: In order to reduce the particle size of the nano-barium titanate / lithium particle powder product doped with E-type elements in situ, at least one of the following three methods can be used: Method 1: During the reaction process of step 2 or (and) step 3, ultrasonic treatment is applied to the reaction system simultaneously; The second method is to perform mechanical crushing and dispersion after step 3, wherein the mechanical crushing and dispersion treatment includes at least one of ball milling and sand milling; The third method is to perform mechanical crushing and dispersion treatment on the intermediate powder product after step 2, and the mechanical crushing and dispersion treatment method includes at least one of ball milling crushing and dispersion and sand milling crushing and dispersion.

13. The method for preparing doped nano-barium titanate / lithium powder according to claim 1, characterized in that: The minimum sintering film-forming temperature of the spherical or nearly spherical nano-barium titanate / lithium particle powder product in-situ doped with E-type elements does not exceed 950°C.

14. Application of the nano-barium titanate / lithium powder material in situ endogenously doped with E-type elements prepared by the preparation method according to any one of claims 1 to 13 in the fields of electronic ceramics, composite materials, coatings, powder metallurgy, multilayer ceramic capacitors, thermistors, piezoelectric ceramics, and battery materials.